Traction mechanism and parameter optimization of curved grousers based on coupled DEM–MBD - Fu Zhang; Le Yang; Yubo Qiu; Yakun Zhang; Zhidan Zhong; Sanling Fu (Journal of Terramechanics, 2027)

Orographic disturbances shaping convective preconditioning over a tropical island - Lanqiang Bai; Yipeng Huang; Qian Liu; Guixing Chen; Shizuo Fu; Qiu Yang; Lei Zhu (Atmospheric Research, 2027)

Fluidized roasting of spodumene ores: geochemical characteristics, phase transformation, and non-isothermal kinetics - Xinran Zhu; Kun Fu; Yuchao Qiu; Gaoyun Tan; Tong Chen; Yuexin Han (Minerals Engineering, 2026)

Comparative genomic epidemiology of food- and patient-derived diarrheagenic Escherichia coli from sentinel surveillance in Southeast China - Xiaomeng Huang; Li Gong; Fuming Liu; Jianhua Mei; Jinkai Li; Siyu Fu; Liyang Qiu; Deyong Zhang; Xiuying Chen (International Journal of Food Microbiology, 2026)

UPF1 promotes wound healing in diabetic foot ulcer by reducing CYP1A1-induced oxidative stress through enhancing EGR1 degradation - Zhi-Yang Qiu; Yun-Lei Ma; Yao-Xue Zhang; Jia Fu; Wei-Cheng Xu; Shao-Jia Kuang; Jia-Qin Xu; Zun-Hong Liang (Molecular Genetics and Genomics, 2026)

Impacts of different ozone treatments on the growth and soil bacterial community of Pinellia ternata - Yucheng Qiu; Xi Feng; Xiangrui Fu; Xiaoying Shang; Yunsheng Zhao; Donglai Ma; Huiyong Fang; Xian Gu (Brazilian Journal of Microbiology, 2026)

Mechanical properties, swelling-shrinkage, and crack resistance mechanisms of plasticity-improved solidified red clay under thermo-hygro conditions - Jinhong Li; Xiang Qiu; Hongyuan Fu; Jiangbin Huang; XiaoMing Fan; Jingchen Chen (Applied Clay Science, 2026)

The impact of ultraviolet-C and ozone treatment on the pineapple fruit quality and the critical regulating factors identification through transcriptome analysis - Jiahong Qiu; Faiz Ur Rahman; Hanxue Xu; Qiunan Zhu; Yufang Fu; Xiaoyang Zhu (Food Research International, 2026)

Agaricus bisporus polysaccharides alleviate high-fat diet-induced cognitive impairment via microbiota-gut-brain axis modulation - Chujing Fu; Kai Ye; Zhichang Qiu; Xinyu Hu; Xiaoxuan Wang; Hang Xiao (Food Research International, 2026)

Assessing present-day tectonic stability, sea-level change, and tsunami hazards from a coastal multi-hazard GNSS station in the southern South China Sea - Qiang Qiu; Linlin Li; Mai Ye; Hongqiang Yang; Xingyu Song; Jian Ping Yin; Tingting Zheng; Jinghe Cao; Peitao Wang; Zhanying Chen; Zhiwen Zhang; Kuilin Xiao; et al. (Engineering Geology, 2026)

Bridging separation and degradation: Rethinking membrane processes as preconcentration and multi-technology coupling platforms for PFAS removal - Xingxing Song; Xingdong Qiu; Liyuan Fu; Yingjie Xia; Xi Chen; Yuan Xiang; Guangyong Zeng (Desalination, 2026)

Rapid co-sintering enables ultra-narrow pore size distribution ceria membranes for high-selectivity U(VI)/V(V) separation - Huanyu Zhou; Fan Yu; Minghui Qiu; Xiaowei Da; Xianfu Chen; Kaiyun Fu; Yiqun Fan (Chemical Engineering Journal, 2026)

Exciton regulation and directional electron transfer in artemisia-derived carbon dots/g-C3N4 heterojunction for enhanced visible-light photocatalytic antibacterial activity - Mingzhu Yuan; Weile Xie; Ran Qiu; Mingxin Zhou; Yangyang Li; Yuanxu Liu; Zibing Liu; Yupeng Yuan; Da Fu; Xiangang Lin (Chemical Engineering Journal, 2026)

Influence of localized fouling on ballast bed performance: A multiscale investigation with soft-shell contact model - Sen Tian; Longlong Fu; Haonan Xi; Yongjia Qiu; Jiawei Zhang; Shunhua Zhou (Transportation Geotechnics, 2026)

Deciphering mechanisms of environmental adaptation, antibiotic tolerance, and potential virulence traits of Pseudomonas baetica isolated from anthropogenic habitat - Mu-Qi Zhang; Yi-Cheng Wang; Ming-Ying Mao; Yin-Qiu Qin; Peng Yan; Hui-Min Fu; Yuan-Xiang Mao; Ji-Cheng Liu; You-Peng Chen; Meng-Jiao Gao (Journal of Environmental Chemical Engineering, 2026)

From agronomic performance to behavioral adoption of biochar‑based slow‑release fertilizer in saline‑alkali rice: A single‑season field trial and survey‑based SEM analysis - Zhixia Wang; Chang Dong; Junqiang Dong; Yang Cheng; Yuan Hu; Dan Liu; Yan Zhang; Zhen Qiu; Yanjiang Cai; Yongfu Li; Cheng Fu; Bing Yu (Journal of Environmental Chemical Engineering, 2026)

Advanced phase-change cooling strategies for high-power electronics: A comprehensive review of engineered fluids, surfaces, and system integrations - Hailing Fu; Mengqi Yu; Yu Liu; Wenjie Qiu; Hao Li; Kunyang Jiang; Zihan Chen; Le Yu; Wenjing Zhang (International Journal of Refrigeration, 2026)

Glacial fluctuations over the past two millennia on the arid northeastern Tibetan Plateau - Weicheng Wang; Jie Wang; Haopeng Geng; Hang Cui; Jinkun Qiu; Zihan Fu (Global and Planetary Change, 2026)

Recent advances in heterologous lactoprotein expression: from host engineering to downstream processing - Yu Qiu; Li Li; Linjie Feng; XiangYu Fan; Xiaolei Fan; Rongbo Guo; Kangqing Fei; Shanfei Fu (Food Bioscience, 2026)

Metal Bi-coupled chiral nanoscale structures enhance spin-polarized electrons to promote photocatalytic CO2 reduction - Dan Wu; Yanni Lang; Liang Xu; Qiyuexin Wang; Qiu Fu; Bingli Li; Xinye Zhao; Zhaoyi Yin; Yongjin Li; Dacheng Zhou; Yangke Cun; Zhiguo Song; et al. (Chemical Engineering Journal, 2026)

A dynamic adaptive electric field regulation strategy for stabilizing zinc anodes based on σ-electron donation - Hongxiang Zhao; Hua Yang; Jiayu Li; Yanwei Fu; Yu Zhao; Yuanshuai Wan; Yue Li; Yuliang Pang; Xingfa Qiu; Wenwen Duan; Weize Wang; Jiali Zhang; et al. (Chemical Engineering Journal, 2026)

Waste akebiae trifoliata-derived WO3 hierarchical tubes efficient detection of ppb-level triethylamine gas at low temperature and application in food freshness detection - Wen-Xiao Li; Jia-Wang Wang; Rui-Long Li; Qiu-Yue Zheng; Bao-Yu Song; Bo-Ya Liu; Li-Xia Zhao; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2026)

Tracing microplastics uptake and translocation in plants using aggregation-induced emission materials - Yang Liu; Siqi Yang; Xia Wang; Wei Du; Nan Fu; Penglin Li; Heng Wei; Fen Zhao; Zijie Qiu; Hao Qiu; Yanxu Zhang; Willie J.G.M. Peijnenburg; et al. (Journal of Hazardous Materials, 2026)

Genome-wide identification of Nitrate Transporter 1/Peptide Transporter Family (NPF) genes in pear (Pyrus bretschneideri) and functional characterization of PbNPF5.7 in fire blight - Lun Li; Chenyang Chen; Keliang Fu; Nie Feng; Taotao Qiu; Yueqi Xu; Qionghou Li; Xin Yan; Jia Tian; Yue Wen; Shaoling Zhang; Xiaosan Huang (Plant Science, 2026)

Impact origin of pink spinel in the Chang’e-6 lunar soils - Linxi Li; Guangyuan Yu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Lihui Jia; Di Zhang; Shitou Wu; Guoqiang Tang; Hao Wang; et al. (Geochimica et Cosmochimica Acta, 2026)

The strategy of nitrate selective inhibition of NOB: transition from complete nitrification to partial nitrification - Teng Guan; Kunming Fu; Yihao Bian; Ruibao Zhang; Shixing Zhang; Tengyue Zhang; Yuanan Cao; Jinyi Liang; Fuguo Qiu (Environmental Research, 2026)

BiOI/Bi4O5Br2/BiOBr double S-scheme heterostructure applied in photocatalysis antimicrobial and degradation: mechanisms and pathways - Liying Huang; Kaixiang Sun; Li Qiu; Yeping Li; Yanyan Fu; Jun Huang; Wenhui Bian; Lijing Huang (Environmental Research, 2026)

Ni/C catalyst modified with Co nanoclusters for highly efficient total hydrogenation of furfural under near room temperature - Qiuju Fu; Huimin Jiang; Wenpeng Xie; Yingxin Zhang; Hengxing Qiu; Shuo Zhang; Xuebo Zhao (Chemical Engineering Journal, 2026)

Fiber-optic SPR sensor based on molecularly imprinted polymers for detection of perfluorooctane sulfonate in water - Hongyou Wu; Bin Liu; Yingying Hu; Juan Liu; Hong Yang; Yue Fu; Yue Zhang; Tao Wu; Ran Tao; Shi Qiu; Jinhui Yuan; Qiang Wu (Chemical Engineering Journal, 2026)

Retraction notice to “Light absorption of black carbon and brown carbon in winter in North China Plain: comparisons between urban and rural sites” [Sci. Total Environ. 770 (2021) 144821] - Jiaxing Sun; Conghui Xie; Weiqi Xu; Chun Chen; Nan Ma; Wanyun Xu; Lu Lei; Zhijie Li; Yao He; Yanmei Qiu; Qingqing Wang; Xiaole Pan; et al. (Science of The Total Environment, 2026)

Retraction notice to “Rapid transition of aerosol optical properties and water-soluble organic aerosols in cold season in Fenwei Plain” [Sci. Total Environ. 829 (2022) 154661] - Aodong Du; Yan Li; Jiaxing Sun; Zhiqiang Zhang; Bo You; Zhijie Li; Chun Chen; Jie Li; Yanmei Qiu; Xingang Liu; Dongsheng Ji; Wenjie Zhang; et al. (Science of The Total Environment, 2026)

Antibacterial activity and mechanism of mangosteen extract garcinone D against Bacillus cereus - Ya-Ya Lei; Guan-Qiu Zhou; Yu-Chen Sun; Jin-Cheng Ma; Fu-Li Liu; Bao-Qi Zhang; Wen Zhang; Li-jing Zhang; Yan-Ze Wang; Ying-Qian Liu (International Journal of Food Microbiology, 2026)

Cloning and functional verification of genes LjHD8 and LjMIXTA1 related to trichome development in Lonicera japonica Thunb. - Xinrui Fan; Jing Fu; Qiu Jiang; Keyang Zhang; Yongqing Zhang; Lingna Wang (Planta, 2026)

Extending Zipf's law: hierarchical scaling analysis and the dynamics of city-level CO2 emissions in China - Sen Liang; Ke Wang; Qiu Jin; Jianjun Zhang; Zhenlin Fan; Iskid Jacquet; Bangning Fu (Sustainable Cities and Society, 2026)

Failure behavior and associated thermal and gas hazards of lithium-ion batteries under typical cargo-fire scenarios in air transport - Fei Li; Zengjiang Zou; Xu Huang; Xudong Cheng; Rong Qiu; Yangyang Fu (Process Safety and Environmental Protection, 2026)

A single strain Priestia sp. confers resistance to rice blast through the activation of plant immune responses - Jirong Shi; Mengyao Yan; Jiajie Lou; Qiuyun Liu; Hanrong Qiu; Xinqing Wu; Jiahong Dong; Liwei Sun; Yinhua Ni; Zhengwei Fu; Haifeng Qian; Tao Lu (Physiological and Molecular Plant Pathology, 2026)

Molecular mechanisms underlying the maintenance of protein homeostasis in pearl gentian grouper under acute high-temperature stress - Qiu-Ting Yang; Ren-Xie Wu; Yan-Shan Liang; Ben-Ben Miao; Su-Fang Niu; Feng-Ling Lei; Fan-Li Long; Zhen-Bang Liang; Yu-Xin Shen; Yu Fu (Journal of Thermal Biology, 2026)

Modification of black bean protein isolate-gum Arabic coacervates by Maillard conjugation and tannic acid cross-linking for stable citronella oil microencapsulation - Haifang Mao; Congle Wang; Benu Adhikari; Jie Chen; Liwei Fu; Liqing Qiu (Innovative Food Science & Emerging Technologies, 2026)

Ascosphaeraapis LncRNA6140 promotes the infection of honeybee larvae through the milR5658-x–ATPase axis - Jianfeng Qiu; Tao Wu; Shuai zhou; Nian Fan; Genchao Gan; Zhitan Liu; Zhongmin Fu; Rui Guo; Dafu Chen (Insect Biochemistry and Molecular Biology, 2026)

Direct visual evidence of S-scheme charge transfer: CeO2 quantum dots anchored on CdS nanosheets for synergistically enhanced photocatalysis - Yaodi Fu; Ke Wen; Shimei Liu; Ping Li; Banpeng Cao; Lihong Cheng; Jingjing Liu; Yi Tang; Xiangshu Chen; Hidetoshi Kita; Lingfang Qiu; Shuwang Duo (Environmental Research, 2026)

Phenolized lignin binders inducing ultrathin SEI of hard carbon for advanced sodium storage - Jinxing Li; Zhipeng Qiu; Fangbao Fu; Weifeng Liu; Jianbin Mo; Dongjie Yang; Xueqing Qiu (Chemical Engineering Journal, 2026)

Directional molecular design of quaternary ammonium deep eutectic solvents: Enabling low-temperature regeneration for CO2 capture - Chao Liu; Boyi Zhang; Shuning Li; Qinghai Long; Xuanang Fu; Huajie Qiu; Huaqiang Fan; Zuoming Zhou; Bihong Lv; Guohua Jing (Chemical Engineering Journal, 2026)

Synergy-driven co-pyrolysis of cotton stalk and agricultural mulch with HZSM-5: Pyrolysis characteristics analysis and multicomponent kinetic modeling - Wenhao Tang; Samuel Mbugua Nyambura; Chao Li; Jieyi Fu; Mingming Liu; Xueru Zhu; Wentao Xu; Shilong Qiu; Hua Li (Biomass and Bioenergy, 2026)

Electrochemical thioester synthesis enabled by phosphine promotion from carboxylic acids and disulfides - Hong Zeng; Ming-Qiu-Hao Fu; Zhi Guan; Yan-Hong He (Molecular Diversity, 2026)

A Hybrid Modal-Decomposition and Formula-Constrained Framework for TBM Penetration-Rate Prediction - Tao Shao; Yiguo Xue; Daohong Qiu; Kang Fu (Rock Mechanics and Rock Engineering, 2026)

Effects of microplastics on carbon and nitrogen cycling in coastal wetlands: A critical meta-analysis - Feng Yuan; Hongyu Chen; Yue Xue; Yongcheng Ding; Qiujun An; Zhian Hu; Yifei Qiu; Jianguo Tao; Jin Luo; Guanghe Fu; Teng Wang; Xinqing Zou (Water Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Dynamic evolution of characteristic flavor molecules in Yunnan arabica coffee during roasting revealed with a multi-omics framework - Yun Niu; Xiaoping Fu; Zhuqing Zhou; Minghua Qiu; Bin Zhou; Jiangping Fan (Food Chemistry, 2026)

Drought as a risk amplifier: The intensifying regime of compound dry-hot events in China - Pengcheng Xu; Dong Wang; Yuankun Wang; Vijay P. Singh; Jianchun Qiu; Xiaolei Fu (Atmospheric Research, 2026)

Iron plaque crystallinity driven by phosphorus gradients directs Cd/As partitioning in rice - Jibo Long; Qian Zhu; Hongyu Fu; Bingyu Li; Yimin Zhou; Zhuoqing Li; Jiaxiang Wang; Cheng Qiu; Qinghai Liu; Ming Lei (Cereal Research Communications, 2026)

Ejecta from Chaffee S Crater in Chang’E-6 Landing Site Constrained by Seifertite-Bearing Norite - Zhan Zhou; Sen Hu; Yubing Gao; Linxi Li; Huicun He; Liang Gao; Mengfan Qiu; Lixin Gu; Xu Tang; Xiaoguang Li; Wei Yang; Yangting Lin; et al. (Journal of Earth Science, 2026)

Docosahexaenoic acid alleviates Ornidazole toxicity related to spermatogenic dysfunction by modulating PPARγ-dependent ER-mitochondrial uncoupling - Chuwei Li; Shanmeizi Zhao; Chongli Shi; Shanshan Sun; Zhaowanyue He; Yao Xu; Lu Zheng; Ting Tang; Shengjie Qiu; Kuan Liang; Hong Zhang; Zhichuan Zou; et al. (Science China Life Sciences, 2026)

IL-17 signaling pathway in monocytes drives the persistent inflammatory cytokine storm caused by Glaesserella parasuis infection in pigs - Peiyi Wang; Aihua Wu; Jianing Niu; Wei Liu; Shulin Fu; Yanyan Zhang; Bingbing Zong; Yinsheng Qiu (Veterinary Microbiology, 2026)

Dynamic prediction of surrounding rock grades in TBM tunnels based on physics–data dual-driven model - Kang Fu; Yiguo Xue; Daohong Qiu; Fanmeng Kong; Jianning Wang (Tunnelling and Underground Space Technology, 2026)

Triple-goal governance of urban agglomerations under SDG 11: A causal inference and deep reinforcement learning framework - Zhiyuan Fu; Bofeng Qiu; Shuo Zhang; YiKe Ma; Tianlian Wang (Journal of Cleaner Production, 2026)

Large-scale gold incorporation in bulk pyrite mediated by arsenic - Zi-Yue Gao; Kun-Feng Qiu; Razvan Caracas; Bing-Cheng Luo; Xin Liu; Zheng-Yu Long; Deng-Yang He; Jia-Nan Fu; Mei-Jing Xu; Hao-Cheng Yu; Zheng-Jiang Ding; Jun Deng (Geochimica et Cosmochimica Acta, 2026)

Integrating probabilistic modeling and geospatial analysis for nationwide assessment of dietary perchlorate exposure in China: Regional disparities, source contribution, and risk implications - Wenbing Huang; Fu Gao; Yuan Zhong; Gaowei Sun; Kaicheng Liu; Chunsheng Qiu; Yubin Liu; Shumin Xiao (Environmental Pollution, 2026)

Validation and applicability analysis of a novel soft-shell contact model for coated granular materials: discrete element modelling and experimental study - Sen Tian; Longlong Fu; Haonan Xi; Yongjia Qiu; Jiawei Zhang; Shunhua Zhou (Computers and Geotechnics, 2026)

Synergistic effects of Ni2P/Ni5P4 heterostructure and N-doped carbon for enhanced asymmetric supercapacitor performance - Minyi Lin; Ting Hu; Wei Qiu; Yuanxiang Fu; Yongbo Wu; Yuhong Luo; Xiaoming Lin (Chemical Engineering Journal, 2026)

The light side of the microbiome in trauma: Mechanism and applications - Han-Yue Luo; Lei-Ming Cao; Kan Zhou; Yi-Fu Yu; Yao Xiao; Guang-Rui Wang; Bing Liu; Qiu-Ji Wu; Xiao-Long Wang; Zhi-Yong Song; Lin-Lin Bu (Chemical Engineering Journal, 2026)

Spiral wrapped in-situ optic fiber tract - Hai Fu; Huifeng Yang; Xin Qiu; Zhi Chen; Yao Zhu; Defa Li; Han Zhang; Zhongjian Xie (Chemical Engineering Journal, 2026)

Stable nitrite accumulation in partial sulfide autotrophic denitrification (PSAD) systems under extremely low S/N ratios - Kunming Fu; Aotong Huo; Jia Kang; Tengyue Zhang; Teng Guan; Xueqin Li; Ruibao Zhang; Yuanan Cao; Shixing Zhang; Jinyi Liang; Yihao Bian; Fuguo Qiu (Journal of Water Process Engineering, 2026)

Transforming soil health with biochar-driven slow-release fertilizers: Emphasis on biochar dual-function for acidification and alkalinization reclamation - Tawasul Ali; Pingyu Qiu; Ping Liu; Nisar Muhammad; Guangquan Chen; Tengfei Fu; Changsheng Peng (Journal of Environmental Chemical Engineering, 2026)

Construction of CuO-ZnO interface electron channels accelerates the methane partial oxidation for high formaldehyde production - Yanjun Li; Chuan Yu; Chen Yang; Keke Tang; Xueyun Zhong; Sijia Weng; Chuying Qiu; Mingli Fu; Daiqi Ye (Journal of Environmental Chemical Engineering, 2026)

Ceramic membrane contactors for removing ammonia from wastewater: 2D model establishment and module scaling-up - Shiji Sun; Kexin Zhang; Dawei Gong; Kaiyun Fu; Xianfu Chen; Minghui Qiu; Ping Luo (Journal of Environmental Chemical Engineering, 2026)

Development of a sporopollenin-hydrogel-Cu2O composite for dye removal: Addressing the dual challenges of agglomeration and ‌embedding of metal nanoparticles in hydrogel-based catalysts - Ying Liu; Jiao Jiao; Qing-Yan Gai; Yi-Bo Qiu; Hong-Yan Zhao; Xiao-Qing Wang; Yu-Jie Fu (Journal of Environmental Sciences, 2026)

The effect of hydrothermal desulfation of Gracilaria on the physicochemical and structural alterations of gel by different temperatures - Yunshuang Jiao; Weijie Qiu; Baoshang Fu; Pengfei Jiang; Libo Qi; Shan Shang (Food Chemistry, 2026)

Ceramic membranes for desalination: Design and fabrication strategies based on the sol-gel method - Weida Shi; Jing Wang; Xianfu Chen; Kaiyun Fu; Minghui Qiu; Yiqun Fan (Desalination, 2026)

Magmatic–hydrothermal mineralization processes in the Xiwukou Sn–W–Rb deposit, Jiangnan orogenic belt: Constraints from multi-mineral U–Pb geochronology - Kun-Yan Wu; Xiao-Ying Gao; Qi Hou; Xiao-Yong Yang; Qiu Wan; Xiang Qian; Fu-Jun Zhong; Gen-Tao Zhou (Mineralium Deposita, 2026)

Accelerated activation of ozone on Fe-doped MnO2 for highly efficient ozone catalytic oxidation of ethyl acetate - Ning Wu; Ming Ouyang; Lei Liu; Chuying Qiu; Ning Wang; Peirong Chen; Junliang Wu; Xiaofei Song; Mingli Fu; Daiqi Ye (Journal of Environmental Sciences, 2026)

Ecological restoration strategies towards environmental suitability and social equity on the Qinghai-Tibetan Plateau - Xuejing Leng; Xiaoming Feng; Jiangxiao Qiu; Jun Wang; Xiao Zhang; Yu Feng; Bojie Fu (Environmental Impact Assessment Review, 2026)

Dietary 4-hydroxy-2,5-dimethyl-3(2 H)-furanone supplementation enhances serum antioxidant capacity and nutrient digestibility in Hu sheep by promoting biofilm formation - Qinghua Qiu; Chuanpei Fu; Lin Li; Kehui Ouyang; Mingren Qu (Animal Feed Science and Technology, 2026)

Warming‐Induced Carbon Vulnerability in Permafrost Forests: A Shift in Q 10 From Continuous to Discontinuous Zones - Changjiang Huang; Tadeo Sáez‐Sandino; Guiyao Zhou; Lingyan Zhou; Tongyao Kong; Yuling Fu; Hongyang Chen; Yimin Zhu; Shuying Qiu; Kui Xue; Chongwei Fan; Lei Cao; et al. (Global Change Biology, 2026)
Permafrost forests harbor vast, climate‐sensitive carbon (C) reservoirs whose vulnerability largely depends on temperature sensitivity of microbial respiration ( Q 10 ). However, substantial uncertainties persist in predicting Q 10 patterns due to complex interactions among multiple ecological factors. Here, we conducted a standardized field survey with controlled incubations across a regional gradient from continuous permafrost (CP) and discontinuous permafrost (Dis‐CP, including sporadic and isolated ones) in the Greater Khingan Mountains to quantify Q 10 values and identify their main ecological controls. We found that the Q 10 values were significantly higher in CP than Dis‐CP forests, indicating a stronger microbial respiratory response to warming in the coldest permafrost regions. Statistical analysis revealed that the soil microbiome was the most important factor explaining Q 10 values in CP forest (47.8%), whereas a distinct set of factors (plant production, fine texture, substrate quality, and mean annual ground temperature) explained the largest proportion (63.2%) of Q 10 variation in Dis‐CP forests. Our findings suggest that warming‐induced permafrost degradation is likely to shift the dominant controls for Q 10 from microbial community to abiotic and plant‐related factors, while enhancing greenhouse gas emissions from permafrost soils.

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Application of improved RRT algorithm by multi-strategy fusion in path planning for robotic manipulator: A case study of multi-posture dragon fruit picking - Bin Zhang; Yuyang Xia; Yang Gu; Zongbin Wang; Qiu Xu; Kairan Lou; Wei Fu (Computers and Electronics in Agriculture, 2026)

Eliminating Microcystis aeruginosa and secondary pollutants via photo-Fenton process over Iron-MOF - Hong- Yu Chu; Zheng-Xing Liu; Jian-Feng Wang; Xuchun Qiu; Fu-Xue Wang; Shao-Long Chen; Hui-Min Yu; Fei Wang; Guang-Chi Liu; Ruo-Xuan Mei; Xin-Jie Li; Xiao-Hang Xu; et al. (Water Research, 2026)

Construction of dual S-scheme WO3/g-C3N4/Bi4O5I2 heterojunctions for efficient bactericidal and BPA degradation under LED light - Jun Huang; Pitao Liu; Shuangxiu Shu; Sibei Fu; Yeping Li; Yanling Li; Li Qiu; Yanyan Fu; Liying Huang; Lijing Huang (Journal of Environmental Chemical Engineering, 2026)

Pyrolysis behaviors of lump sub-bituminous coal. Part 2: Effect of particle size - Zong-Pin Fu; Le-Le Qiu; Yi-Bin Huang; Yun-Peng Zhao; Jian Zhou; Jing Liang; Jian Xiao; Fang-Jing Liu (Fuel, 2026)

Design and optimization of triply periodic minimal surface structure flow channels in proton exchange membrane fuel cells based on genetic algorithm - Lirong Fu; Yiwen Tang; Jinyi Liu; Mingwei Li; Na Qiu (Fuel, 2026)

Impact of ultrasound-assisted braising on Xinjiang-style jar stewed mutton flavor compounds - Xinyu Chen; Tengbin Wang; Huabo Fu; Siqi Qiu; Yuhan Duan; Xulong Li; Jingyun Wang; Xin Guo; Shiling Lu (Food Chemistry, 2026)

Economic benefits of carbon source selection for polyphosphate-accumulating organisms in enhanced biological phosphorus removal - Jing Yuan; Liping Chen; Xiaojing Xie; Hang Chen; Xiaodong Du; Acong Chen; Haixin Zheng; Fu Huang; Sijia Ji; Zemin Li; Xianghui Liu; Zhiyi Deng; et al. (Environmental Research, 2026)

Succinic acid pretreatment of corn cob for production of xylooligosaccharides and biomass pellets - Zhenchang Wang; Yuejie Qiu; Youhong Fu; Dehua Li; Jiahao Zhuang; Jianxin Jiang (Biomass and Bioenergy, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Stabilization stage dissolved oxygen and contact-stabilization time ratio synergistically govern quorum sensing-mediated sludge bulking in the high-rate contact-stabilization process - Zhongqi Jiang; Shan Qiu; Mengxuan Deng; Mengqi Fu; Zikun Jin; Mu Yuan; Wei Zhang; Chuandong Wu (Water Research, 2026)

Multi-channel fusion prediction of TBM tunneling thrust based on multimodal decomposition and reconstruction - Kang Fu; Yiguo Xue; Daohong Qiu; Peng Wang; Haolei Lu (Tunnelling and Underground Space Technology, 2026)

Impact of road density on the coupling of forest resilience and fragmentation - Weiguo Qiu; Miaomiao Liu; Qingjie Fu; Zhanyong Wang; Lanyi Zhang; Li Jiang; Mengwei Li; Xisheng Hu (Transportation Research Part D: Transport and Environment, 2026)

The glutamyl-prolyl-tRNA synthetase 1 inhibitor halofuginone exerts synergistic antitumor effects with bortezomib in colon cancer cells - Han Lin; Ying Yan; Chenyu Qiu; Junqi Wang; Wenying Fu; Chongchong Shu; Yinghua Chen; Chenxin Xu; Shaotang Li; Yiqun Xia; Jundixia Chen; Yunzhi Chen; et al. (Toxicology and Applied Pharmacology, 2026)

Efficient charge carrier separation over [Mo7O24]6- polyanions-intercalated porous graphitic carbon nitride for remarkably enhanced photocatalytic performance - Jiajia Liu; Yaodi Fu; Shimei Liu; Ping Li; Banpeng Cao; Lihong Cheng; Jingjing Liu; Yi Tang; Xiangshu Chen; Hidetoshi Kita; Lingfang Qiu; Shuwang Duo (Process Safety and Environmental Protection, 2026)

Restricting roles of arbuscular mycorrhizal fungi in cadmium uptake and translocation in tomato - Junli Liu; Gaoyang Qiu; Xiaodong Chen; Junbo Zhang; Chenxi Fu; Qinglin Fu; Aiqun Chen; Jun Zhang; Wenbin Tong; Bin Guo (Journal of Hazardous Materials, 2026)

Do biodegradable plastic residues pose lower ecological risks to crops than conventional plastic residues? A meta-analytic comparison - Feng Yuan; Teng Wang; Hongyu Chen; Yongcheng Ding; Jianguo Tao; Yue Xue; Linjie Zhang; Haiyan Lin; Baojie Li; Yifei Qiu; Guanghe Fu; Xinqing Zou (Journal of Hazardous Materials, 2026)

Genesis and prospecting significance of the Xiaodonggou granites in the eastern Central Asian Orogenic Belt: Evidence from geochronology, geochemistry, and Hf isotope characteristics - Lele Qiu; Peiwen Chen; Renchang Mi; Zhujun Liu; Yong Fu; Qingdong Zeng (Journal of Geochemical Exploration, 2026)

Delivery of carbonaceous materials to the Moon - Linxi Li; Mengfan Qiu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Yuyang He; Shitou Wu; Hao Wang; Guoqiang Tang; Di Zhang; et al. (Icarus, 2026)

Electrochemical aptasensor based on Zr-MOF@Ag nanocomposite for the rapid detection of chloramphenicol in honey, milk and lake water - Zhaoyuan He; Chengxiang Fu; Shuling Meng; Jiaqi Luo; Jieke Qiu; Jianing Huang; Xiaoge Duan; Jiakang He; Jinzi Wang; Hailan Chen (Food Chemistry, 2026)

The low R = d/d high-entropy strategy enables high-performance sodium layered oxide cathode materials - Jun-Jie Liao; Min Wen; Wei-Wei Yuan; Qi-Lin Zheng; Kang Chen; Fu-Sheng Zhou; Zhen-Xin Qiu; Su-Yun Wang; Li-Li Wang; Lituo Zheng; Yiyin Huang; Jia-Xin Li; et al. (Chemical Engineering Journal, 2026)

Carbon dots with concurrent antibacterial, anti-inflammatory, and osteogenic activities for visualized therapy of infected bone defects through modulating bone immune microenvironment - Yan Xia; Jinyan Hu; Jianjun Qiu; Panfeng Wang; Lei Li; Shuogui Xu; Bijiang Geng; Shuming Pan; Qingge Fu (Chemical Engineering Journal, 2026)

Characterization of the genetic architecture of adult plant resistance to sharp eyespot in Chinese wheat germplasm - Caiyun Liu; Wenling Zhai; Ningning Kang; Yanjiang He; Bisheng Fu; Wei Guo; Qiaofeng Zhang; Jin Cai; Ying Liu; Guang Qiu; Hua Jiang; Fujie Liu; et al. (Theoretical and Applied Genetics, 2026)

Synergistic Neuroprotection of Combined Shenmai and Hypothermia in Cerebral Ischemia–Reperfusion Injury via ERK-Dependent Anti-inflammatory Effects - Yuan Wang; Hangui Ren; Yufei Qiu; Rongchen Dai; Mengfan Liu; Shiting Mo; Yibo Zhang; Wang Fu; Qianqian Bi; Yongpeng Wang; Yunuo Zhou; Zhichao Xi; et al. (Molecular Neurobiology, 2026)

Metagenomic insight into the ecological effects of the plastisphere in coastal salt marshes - Feng Yuan; Junjie Wang; Ming Lu; Qihang Liao; Teng Wang; Yue Xue; Hongyu Chen; Yongcheng Ding; Guanghe Fu; Penghua Qiu; Xinqing Zou (Marine Pollution Bulletin, 2025)

Molecular-scale investigation on the role of MnO2–mediated oxidation in regulating photochemical reactivity of dissolved organic matter - Rui Chai; Huanxin Ma; Hengyi Fu; Ke Sun; Chunhua Feng; Chao Jin; Rongliang Qiu; Shishu Zhu (Water Research, 2025)

Baicalin-aluminum complexes inhibit growth and suppress virulence of enterotoxigenic Escherichia coli in vitro - Chun Ye; Xingyue Li; Yunqi Liu; Yuqian Chen; Ming Zhao; Ronghua Yin; Qirong Lu; Jin Liu; Yu Liu; Shulin Fu; Yinsheng Qiu (Toxicon, 2025)

Inversion and mapping of soil alkali-hydrolyzable nitrogen in farmland using satellite remote sensing and machine learning - Jinkai Qiu; Wei Zhang; Xiuying Xu; Yongcai Ma; Xiaoming Fu; Wenqiang Shi (Soil and Tillage Research, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Mussel-inspired coating anchored polyquaternium functionalized nonwoven fabrics for microplastic adsorption - Yuanshuai Wan; Yanjun Jia; Yonggui Guo; Jianteng Sun; Maofeng Liang; Lichao Gao; Haidong Cao; Tiantian Liu; Hongxiang Zhao; Yuliang Pang; Yanwei Fu; Yu Zhao; et al. (Journal of Environmental Chemical Engineering, 2025)

Application of microbial electrolysis cells in enrichment of anammox bacteria - Qi Gao; Liang Fu; Jing Wei; Xiao-Chun Wang; Xiang Xiao; Yang-Yang Yu; Liang Cheng; Yu-Hao Qiu; Shan-Wei Li (Journal of Environmental Chemical Engineering, 2025)

Evolution of water-soluble organic aerosol composition from clean days to haze episodes in rural area of North China Plain - Chun Chen; Long Jia; Zhiqiang Zhang; Jian Gao; Yanmei Qiu; Junling Li; Rui Gao; Ping Li; Qun Zhang; Zhijie Li; Jiaxing Sun; Nan Ma; et al. (Journal of Environmental Sciences, 2025)

Presence of a queen (Apis mellifera) reduces the sensitivity of worker bees to environmental risks - De Fang Niu; Qiu Lan Zheng; Bin Yuan; Xiao Ling Su; Cui Ping Zhang; Yuan Yuan Lu; Ping Liu; Fu Liang Hu; Huo Qing Zheng (Journal of Asia-Pacific Entomology, 2025)

Effects of flow-guiding block on water transport and performance in modified PEMFC gas flow channel - Lirong Fu; Baoshuo Yu; Shengwei Wu; Jinyi Liu; Huadong Lin; Na Qiu (Fuel, 2025)

Critical role of crosstalk through the gut-liver and gut-kidney axes in mediating organ-specific toxicity induced by foodborne and waterborne rare earth elements - Zhuozhong Fu; Wenxing Li; Hao Qiu; Ana Romero-Freire; Erkai He (Environmental Pollution, 2025)

Task-specific deep eutectic solvents: Intelligent molecular design for on-demand CO2 capture and release - Xuanang Fu; Huajie Qiu; Anteng Dai; Qinghai Long; Chao Liu; Zuoming Zhou; Guohua Jing; Bihong Lv (Chemical Engineering Journal, 2025)

Enhanced piezoelectric demulsification for high-efficiency separation of water-in-oil (W/O) emulsions based on biomimetic PVDF/liquid metal nanofiber membranes - Wen-Qiang Qiu; Jia-Qi Luo; Qing-Ke Luo; Yan-Ping Zhao; Zhi-Yu Xue; Jing-Song Tang; Hai-Feng Lu; Yi Zhang; Da-Wei Fu (Chemical Engineering Journal, 2025)

Supercritical CO2-assisted pressure homogenization for exfoliating natural graphite toward high-performance graphene cathodes in aluminum-ion batteries - Yue Wu; Jianmin Feng; Li Wang; Jiacheng Qiu; Xuan Song; Xuwang Fu; Ziqi Luo; Jiahan Ma; Xiaoyu Yu; Lei Dong; Yan Han; Conglai Long; et al. (Chemical Engineering Journal, 2025)

Fungal and bacterial necromass: Opposite drivers of mineral-associated organic carbon gains and losses - Zihuan Fu; Yuxuan Zhang; Weiwen Qiu; Waqas Mohy-Ud-Din; Zhifeng Yan; Yakov Kuzyakov (Soil and Tillage Research, 2025)

First demonstration of spaceborne L-band bistatic single-polarization single-baseline SAR interferometry on the retrieval of forest vertical structural information - Yang Lei; Weiliang Li; Yanghai Yu; Xiaotong Liu; Jie Xu; Anmin Fu; Jie Wan; Changcheng Wang; Wenli Huang; Zixuan Qiu; Tao Li; Haiqiang Fu; et al. (Remote Sensing of Environment, 2025)

Evaluation of harmful impact of low concentration cylindrospermopsin through zebrafish behavioral endpoints under multiple life stages - Minghui Fu; Yining Zhang; Linjie Luo; Minglu Wu; Liyan Teng; Jiandong Mu; Guohua Xiao; Yanyang Xu; Jing Qiu; Tingting Chai; Yongzhong Qian; Guijie Hao; et al. (Journal of Hazardous Materials, 2025)

A beneficial exploration and recommendations for the use of hydrophobic materials in ecological protection of strongly weathered carbonaceous mudstone slopes - Huanyi Zha; Ling Zeng; Hongyuan Fu; Xiang Qiu; Peng Zhuo (Journal of Cleaner Production, 2025)

Spatiotemporal evolution patterns of mining-induced overburden damage based on microseismic event response analysis - Xiao Yang; Longqing Shi; Mei Qiu; Jin Han; Xingyue Qu; Song Fu (Journal of Applied Geophysics, 2025)

Effect of desalination-related pH shift on whey protein structure and digestion: Insights from spectroscopy, molecular dynamics simulation, and peptidomics - Meng-Qi Liu; Yun Chen; Hong-Fu Zhao; Ying-Chao Qiu; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

Development and characterization of Agriophyllum squarrosum starch nanoparticles for enhanced pickering emulsification stability - Lihong Han; Xiaofan Yang; Wenting Fu; Yuanyuan Li; Zhaojun Wei; Donghong Liu; Shuang Qiu (Food Chemistry, 2025)

Sustainable lignin-derived heteroatom-doped defective carbon cathodes toward superior zinc-air rechargeable batteries - Sabarinathan Ravichandran; Shuhua Hao; Fangbao Fu; Xihong Zu; Xueqing Qiu; Wenli Zhang (Chemical Engineering Journal, 2025)

Spirooxazine-based ultraviolet photoelectric nanogenerator: material design, alternating-current output regulation, and object recognition applications - Weihua Qiu; Yinghao Zhang; Xiaowei Fu; Liang Jiang; Jingxin Lei; Yuan Lei (Chemical Engineering Journal, 2025)

Versatile nano-NH2-MIL-53(Al) tailored excellent fire resistance, mechanically robust, and ultraviolet to high-energy blue light blocking clear carboxymethyl cellulose films - Qiu Fu; Jingyuan Zhang; Ying Qin; Weimin Guo; Kuo Zhang; Tianyuan Xiao; Jiang Chang; Lijian Sun; Haiqiang Shi (Carbohydrate Polymers, 2025)

On-chip single-cell mass spectrometry for streamlined metabolic exploration enabled by a reversibly-bonded microfluidic platform - Jiacheng You; Anqi Chen; Jianxiong Qiu; Yaling Ye; Chongchong Mei; Guanghou Fu; Baiye Jin; Luhong Wen (Analytica Chimica Acta, 2025)

Unveiling the mystery of chlorine radical in water by a simple methanol-based spin trapping - Pu Wang; Lingli Wang; Ronghui Xiao; Sifan Qiu; Jinhui Cao; Yu Fu; Shandi Bai; Zhaohui Wang (Water Research, 2025)

Short-impending decision-making for TBM tunneling control based on loading phase data - Kang Fu; Yiguo Xue; Daohong Qiu; Peng Wang (Tunnelling and Underground Space Technology, 2025)

Genomic insights into the reticulate evolution of viviparous Phrynocephalus lizards on the Qinghai-Tibetan Plateau - Xianguang Guo; Zhongyi Yao; Bo Cai; Xiao Xiao; Qiwei Xu; Ying Chen; Lin Cui; Xia Qiu; Jinzhong Fu; Yin Qi; Weizhao Yang (Molecular Phylogenetics and Evolution, 2025)

The impacts of polypropylene microplastics on carbon and nitrogen cycling in coastal wetlands: Field evidence - Feng Yuan; Yue Xue; Zhuoyue Zhang; Jianguo Tao; Yuyang Song; Hongyu Chen; Qihang Liao; Haiyan Lin; Ming Lu; Yongcheng Ding; Teng Wang; Ruize Yang; et al. (Journal of Hazardous Materials, 2025)

Study of changes in volatile flavor substances during the processing and storage of mutton ham - Xinyu Chen; Huabo Fu; Siqi Qiu; Yuhan Duan; Xulong Li; Xin Guo; Shiling Lu; Jingyun Wang (Food Research International, 2025)

Energy-efficient CO₂ capture using a biphasic tertiary-amine ionic liquid with reversible phase behavior - Qinghai Long; Yutao Bai; Anteng Dai; Huajie Qiu; Xuanang Fu; Xiaoyun Chen; Chao Liu; Waseem Hayat; Bihong Lv; Guohua Jing; Zuoming Zhou (Chemical Engineering Journal, 2025)

Surrounding rock grade identification of deep TBM tunnel based on data decomposition and model fusion - Kang Fu; Daohong Qiu; Yiguo Xue; Fanmeng Kong; Huimin Gong (Tunnelling and Underground Space Technology, 2025)

A bifunctional polyacrylamide-alginate-TiO2 hydrogel solar evaporator for integrated high-efficiency desalination and photocatalytic degradation - Xinye Xu; Junxiao Qiu; Zheng Li; Anni Fu; Shutong Yuan; Hai Li; Baoyang Lu (Desalination, 2025)

Tri-layered immune-competent intestinal chip with synchronous peristaltic-mucosal flow dynamic for Allergenicity assessment of food proteins - Wenjing Zhang; Jiangbing Shuai; Hui Qiu; Xiaofeng Zhang; Ke Li; Jinru Zhou; Huan Li; Linglin Fu (Chemical Engineering Journal, 2025)

An ionic liquid phase change absorbent capable of low-temperature regeneration: Investigation of phase change and regeneration mechanism - Huajie Qiu; Qinghai Long; Yutao Bai; Xuanang Fu; Chao Liu; Guohua Jing; Zuoming Zhou; Bihong Lv (Chemical Engineering Journal, 2025)

Lanthanum-based hydrogels for simultaneous removal of trace phosphorus and algae - Yan Zhang; Qian Xie; Cheng Fu; Zhen Qiu; Zechao Zhuang; Ting Wang; Yunying Fang; Yongfu Li; Yanjiang Cai; Huajun Feng; Bing Yu (Chemical Engineering Journal, 2025)

Analgesic Effects of Acupressure on Jing-jiaji Acupoints in a Rat Model of Cervical Spondylotic Radiculopathy - Shang-Hong Jiang; Song Yang; Ling Meng; Ling-Yao Xie; Jia-Ni Yang; Si-Qi Li; Ke-Ying Liao; Zhi-Fang Qiu; Yao-Yao Xiao; Man-Di Fu; Zhi-Li Liu; Xue-Yu Jiang (Molecular Neurobiology, 2025)

Quorum-sensing Inhibitory Activity of Xanthones from Hypericum Curvisepalum N. Robson Against Chromobacterium Violaceum - Hong Zeng; Qiu-Ying He; Sheng-Qiang Yang; Xiao-Lian Wei; Jia-Zi Luo; Jing-Kai Zhou; Rong-Bing Fu; Li-Ping Teng; Zhong-Bo Zhou (Current Microbiology, 2025)

A new network-level multi-objective optimization of the heat rejection system for megawatt space nuclear power systems - Yiheng Fei; Jianghan Fu; Chenglong Wang; Suizheng Qiu (Annals of Nuclear Energy, 2025)

Integrating microbial community dynamics and emerging contaminants (ECs) for precisely quantifying the sources in groundwater affected by livestock farming - Kai Liu; Jinrong Qiu; Chih-Huang Weng; Zhongen Tang; Renchuan Fu; Xiaojun Lin; Xiujuan Wang; Na Liu; Jingwen Zeng (Journal of Hazardous Materials, 2025)

Self-organizational origin of oscillatory zoning in pyrite: A coupled diffusion–reaction model and pH-dependent As adsorption feedback mechanism - Wenhong Johnson Qiu; Mei-Fu Zhou (Geochimica et Cosmochimica Acta, 2025)

Achieving partial nitrification and denitrification coupled with simultaneous partial nitrification, anammox, and denitrification (PND-SNAD) by the inhibition of sulfide to accomplish stabilized nitrogen removal - Yihao Bian; Kunming Fu; Ruotong Xu; Teng Guan; Aotong Huo; Ruibao Zhang; Xueqin Li; Fuguo Qiu; Yongji Zhang (Environmental Research, 2025)

Hybrid DNA nanomaterial and three-directional hybridization chain reaction enable electrochemical diagnosing metastatic lymph nodes of breast cancer by one-step exosome sensing - Zhihao Zhang; Ronghao Hu; Di Fu; Weijing Liu; Jie Qu; Yue Wang; Xianghu Zeng; Xin Zhao; Xiangyue Meng; Binxu Qiu; Xin Jiang; Bofu Liu; et al. (Chemical Engineering Journal, 2025)

The combination of linkage mapping, genome-wide association study, and dynamic transcriptome analysis reveals conserved candidate genes for salt tolerance in maize - Ziyi Xiao; Zhenyuan Pan; Xinxin Liu; Xueqing Zheng; Guantao Wang; Yayu Fu; Mengmeng Li; Bin Hou; Xuhua Li; Ming Zhang; Chunlan Jia; Fazhan Qiu (Theoretical and Applied Genetics, 2025)

Flash elimination of nano-/microplastics from complex matrices with record efficiency and sustainability - Nuan Liu; Yingxin Ji; Feng Tang; Jianxin Fu; Chuntian Qiu; Rui Wang; Zhiyang Zhang; Lingxin Chen; Guoqing Wang (Chemical Engineering Journal, 2025)

Orthosilicic Acid Promotes Diabetic Wound Healing Through the PI3 K/AKT/mTOR Signaling Pathway - Xinhui Wu; Jincheng Liu; Wenting Song; Lanxia Wu; Qingyang Fu; Junfei Chen; Qiu Li (Biological Trace Element Research, 2025)

Seasonal variations in nutrient changes during sludge anaerobic digestion combined with thermal hydrolysis and deep dewatering - Bing Zhao; Yuxin Wang; Jiawei Wang; Yinquan Qiu; Fenfen Zhu; Qian Chen; Yuhui Zhang; Huan Wang; Xingmin Fu (Waste Management, 2025)

Enhanced immobilization of Cd(II) by successive isomorphic substitution with Ca(II) and Mg(II) from ternary layered double hydroxides - Xiaoxian Zhang; Junnan Rui; Shuyi Yang; Rongbing Fu; Yuping Qiu (Journal of Hazardous Materials, 2025)

Highly efficient photocatalytic removal of NO and synchronous inhibition of NO2 via heterojunction formed by ZnAl-LDH and MXene-Ti3C2-derived TiO2@C - Kaili Wu; Yacen Tang; Yirui Qiu; Haibo Zhou; Xingyan Liu; Panyin Wang; Youzhou He; Shimeng Pan; Yuyu Fang; Min Fu; Siping Wei; Fan Dong (Journal of Hazardous Materials, 2025)

A novel Ce-Bi2MoO6/CeVO4 Z-scheme heterojunction for peroxymonosulfate activation toward levofloxacin photodegradation - Xin Nie; Jun Li; Guohua Dong; Yong Li; Xinjia Zhang; Wenzhi Zhang; Qiu Fu; Tianyuan Xiao; Liming Bai (Journal of Environmental Chemical Engineering, 2025)

Co-deposition of CuxFey on nickel foam promotes NH3 desorption to enhance nitrate reduction activity and ammonia selectivity - Guangyuan Meng; Xinwan Zhang; Wenzhao Fu; Yannan Qiu; Di Yin; Peng Chen; Daqing Jia; Zhihao Lu; Lehua Zhang (Journal of Environmental Chemical Engineering, 2025)

In vitro digestion and fermentation characteristics of Agrocybe cylindracea polysaccharides and their interaction with the gut microbiota - Chujing Fu; Kai Ye; Zhichang Qiu; Gaoxing Ma; Shiguo Chen; Hang Xiao (Food Research International, 2025)

Improving the quality of frozen steamed stuffed buns after freeze-thaw cycles: Synergistic effects of cellulase, xylanase and sourdough - Zhao-Qiu Fu; Xiao-Hong Sun; Ke-Xue Zhu; Xiao-Na Guo (Food Bioscience, 2025)

Effects of tourmaline on anaerobic ammonia oxidation process: Mechanistic Understanding and performance evaluation - Mu Yuan; Xiaohan Jiang; Shan Qiu; Baojian Jing; Shuoqi Ren; Jue Wang; Mengxuan Deng; Mengqi Fu; Zhongqi Jiang; Fengxia Deng; Jinghui Wang; Jie Qiu (Chemical Engineering Journal, 2025)

In situ multifunctional gel for hormone-immune therapy of ovarian cancer and prevention of postoperative adhesion - Yankun Zhang; Yanbin Shi; Hengchang Zang; Xiaogang Zhao; Xianglei Fu; Shengnan Qiu; Yuan Zhang; Yingying Liu; Xiaoyu Wan; Zengmei Li; Yaqi Li; Jiamin Zhou; et al. (Chemical Engineering Journal, 2025)

Boosting selectivity in glucose hydrogenation to sorbitol by optimizing Fe distribution in alloys and supports - Yixin Luo; Jingnan Yang; Fu Li; Xiaomei Zhou; Tongyan Yu; Qingxin Guan; Mo Qiu; Wei Li (Chemical Engineering Journal, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

Combined toxicity of decabromodiphenyl ethane and Pb on earthworms (Eisenia fetida) based on multiple biomarker responses - Meiqing Jin; Yuanchao Sun; Bing Chai; Minghu Wang; Yuping Wu; Weihong Wu; Qingwei Zhou; Linlin Qiu; Jia Du; Li Fu (Journal of Soils and Sediments, 2025)

Magnetic proxy in the Heqing drill core revealed Indian Summer Monsoon variations linked with AMOC at the orbital -scale during the late Pleistocene - Xinwen Xu; Xiaoke Qiang; Xubin Li; Haijun Qiu; Hui Zhao; Chaofeng Fu; Ziyi Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Development of weakly euxinic basin environments in the Phanerozoic oxic ocean: Insights from Fe speciation and Mo isotopes of Devonian pyrite-bearing black shales, Dajiangping pyrite mine, South China - Wenhong Johnson Qiu; Mei-Fu Zhou; John Malpas; Jie Li; Zerui Ray Liu; Yafei Wu (Global and Planetary Change, 2025)

Multi-omics joint analysis: Pachymic acid ameliorated non-alcoholic fatty liver disease by regulating gut microbiota - Guilin Ren; Yiyou Lin; Yilong Fu; Fucai Liu; Ruiqi Wang; Congcong Zhang; Jiannan Qiu; Lin Chen; Xiaobing Dou (Food Research International, 2025)

Carbon monolith supported Fe-Based catalyst Boosts olefins production performance of Fischer-Tropsch synthesis via enhanced Mass-Transfer effect - Yang Wang; Ruosong He; Kaixuan Huo; Pei Dong; Xiaoli Fu; Shujie Sun; Feng Qiu; Yiwu Lu; Qiang Liu; Guangbo Liu; Noritatsu Tsubaki; Mingbo Wu (Chemical Engineering Journal, 2025)

Efficient removal of organic pollutants by metal–organic framework derived Co-N@C hollow multi-shell nanoreactors: Size-exclusion and confinement effect - Zhen Qiu; Guanda Shen; Zefeng Ruan; Xin Zeng; Hailu Fu; Yongfu Li; Bing Yu (Chemical Engineering Journal, 2025)

Compliant picking control of dragon fruit picking robot based on adaptive variable impedance - Zongbin Wang; Kairan Lou; Bin Zhang; Yang Gu; Qiu Xu; Wei Fu (Biosystems Engineering, 2025)

New pathway under light: conversion of furans to pyrroles - Yue-Liu-Ting Fu; Jun-Wei Shi; Peng Chen; Wen-Jing Xiao; Liang-Qiu Lu (Science Bulletin, 2025)

Integrative proteogenomic and pharmacological landscape of acute myeloid leukaemia - Hanlin Wang; Jun-Yu Xu; Tao Wang; Gaoya Xu; Guanghao Luo; Mingya Zhang; Gusheng Tang; Chang Wang; Libing Wang; Weijia Fu; Xiong Ni; Linhui Zhai; et al. (Science Bulletin, 2025)

S-scheme heterojunction photocatalyst constructed by growing Bi5O7I on Bi3O4Br：Antimicrobial and degradation performance under LED light - Yanling Li; Yeping Li; Heman Xie; Li Qiu; Shuai Liu; Menghao Zhu; Jun Huang; Yanyan Fu; Lijing Huang (Journal of Environmental Chemical Engineering, 2025)

A review of redox-active polymers for selective electrochemical removal of uncharged organic pollutants from water - Zhen Qiu; Guanda Shen; Wenxin Yan; Xin Zeng; Maonan Jiang; Yongfu Li; Hai Xiang; Hailu Fu; Chang Liu; Bing Yu (Journal of Environmental Chemical Engineering, 2025)

Dietary pyridoxine promoted muscle protein deposition relating to PI3K/AKT/TOR pathway and the ubiquitin proteasome system in grass carp (Ctenopharyngodon idella) - Li-Fu Gong; Xiao-Qiu Zhou; Lin Feng; Pei Wu; Wei-Dan Jiang; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Fa-Li Wu; Yang Liu (Food Bioscience, 2025)

A high-performance color conversion and UV to blue light blocking materials enabled by iron-coordinated cellulose - Lijian Sun; Jingyuan Zhang; Ying Qin; Weimin Guo; Kuo Zhang; Jiang Chang; Tianyuan Xiao; Wei Wang; Qiu Fu (Chemical Engineering Journal, 2025)

A novel injectable sodium alginate/chitosan/sulfated bacterial cellulose hydrogel as biohybrid artificial pancreas for real-time glycaemic regulation - Xiang Zhao; Wei Xue; Weixiao Ding; Yalei Qiao; Xuehui Chu; Yudong Qiu; Min Tang; Dongping Sun; Xiao Fu (Carbohydrate Polymers, 2025)

Coordinated transcriptional regulation of carbohydrate-related pathways contributes to the difference of starch accumulation between starchy cassava and sugary cassava - Zehong Ding; Lili Fu; Ganlu Chen; Yan Yan; Weiwei Tie; Xianwei Meng; Jinghao Yang; Xianjin Qiu; Jiaming Zhang; Wei Hu (Carbohydrate Polymers, 2025)

Permian thermal pulse event in Southwestern China and its resource and environment effects - Qianqian Feng; Nansheng Qiu; Xiaodong Fu; Tenger Borjigin; Qingyong Luo; Chuanqing Zhu (Global and Planetary Change, 2025)

Potential effects of pH changes in the micro-environment during desalination on infant powder: The perspective of pH shift affecting whey protein molecular structure and function - Meng-Qi Liu; Wen-Xiu Zhi; Hong-Fu Zhao; Ying-Chao Qiu; Kun-Long Wang; Ying-Hua Zhang; Zhi-Shen Mu (Food Hydrocolloids, 2025)

Effect on heat treatment on the physical stability, interfacial tension and in vitro digestion of whey protein-stabilized ω-6/ω-3 fatty acid balanced pumpkin seed oil complex condensate - Yini Fu; Jing Wang; Xiaoxiao Liu; Yongqing Ni; Zhiya Niu; Ligong Qiu; Zhanxia Liu; Changqing Wei (Food Hydrocolloids, 2025)

Photothermal-photocatalytic bifunctional highly porous hydrogel for efficient coherent sewage purification-clean water generation - Xinye Xu; Qi Liu; Junxiao Qiu; Qi Zhao; Shutong Yuan; Hai Li; Zheng Li; Anni Fu; Jingkun Xu; Baoyang Lu (Desalination, 2025)

The application of pressure-driven ceramic-based membrane for the treatment of saline wastewater and desalination–A review - Yuehua Zhang; Ting Chen; Xianfu Chen; Kaiyun Fu; Minghui Qiu; Yiqun Fan (Desalination, 2025)

Numerical study on the effect of intersection angle and loading magnitude on leakage-induced ground collapse - Xin-Zhuo Xie; Qiu-Hua Shi; Jian-Fu Lin; Zhen Guo; Wei-Qiang Feng (Computers and Geotechnics, 2025)

Hollow FeNi Prussian blue nanocages with enhanced peroxidase-mimicking activity for colorimetric detection of mercury ions and L-cysteine - Dai Lu; Xing Tian; Zixuan Fu; Sizhao Yang; Yixing Qiu; Yupei Yang; Bin Li; Wei Wang (Chemical Engineering Journal, 2025)

Optimization of TBM Tunneling Parameters for Deep Buried Tunnel Based on Rock Cluster Grading and Strata Intelligent Identification - Kang Fu; Daohong Qiu; Yiguo Xue; Wenqing Zhang; Tao Shao (Rock Mechanics and Rock Engineering, 2025)

Mulberry leaf extract reduces damage by regulating the oxidative response, immune response and intestinal flora of largemouth bass (Micropterus salmoides) under chronic heat stress - Bing Fu; Donglai Zhou; Xiaotong Qiu; Jieqiu Zheng; Qiong Yang; Yang Xiao; Sentai Liao; Qingrong Li; Dongxu Xing (Frontiers in Marine Science, 2025)
Chronic heat stress (HS) induces oxidative damage, low immunity, and intestinal flora disturbance of fish, posing great challenges to the aquaculture industry. As an important plant extract, mulberry leaf extract (MLE) has been shown to have antioxidant and immune-boosting properties. This study evaluated the protective effect of dietary MLE on HS-induced liver injury and intestinal flora disturbance in Largemouth bass ( Micropterus salmoides ) based on oxidative damage parameters, immune parameters, and intestinal flora composition. Fish were randomly assigned into three groups: CON group (ambient temperature, 26°C, basal diet), HS group (33°C, basal diet), and HS + MLE group (33°C, basal diet supplemented with 9 g/kg MLE). HS significantly decreased the final body weight, specific growth rate, intestinal villus length, muscular layer thickness, ACE and Chao1 indices, and lipase, trypsin, total superoxide dismutase (T-SOD), glutathione peroxidase (GPx), alkaline phosphatase (AKP), and lysozyme (LZM) activities, but significantly increased the feed conversion rate, aspartate aminotransferase (AST) activity, reactive oxygen species (ROS), malondialdehyde (MDA), complement 3 (C3) contents, and the relative abundances of Proteobacteria and Plesiomonas . Compared with the HS group, dietary MLE significantly improved lipase, trypsin, GPx, ACP, and LZM activities, and ACE and Chao1 indices in intestine, but significantly decreased the numbers of vacuoles and inflammatory cells, AST activity, and the GLU, MDA, and ROS contents. Dietary MLE also significantly up-regulated the mRNA expressions of gpx , tg f-β , il-10 , jnk2 , and bcl-2 , but down-regulated the mRNA expressions of il-8 , tnf-α , caspase-3 , atf4 , chop , ire1, traf2 , jnk1 , TRPV , MCU , and VDAC in liver. In conclusion, dietary supplementation with 9 g/kg MLE could improve the growth, immunity, and diversity of intestinal flora in heat-stressed largemouth bass, and alleviate hepatic injuries by regulating inflammation, oxidative stress, and apoptosis, providing a theoretical basis for the development of MLE as a treatment against HS.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Calcium and iron isotope fractionation during felsic magma differentiation - Qiu-Yun Guan; Jin-Xiang Li; Ya-Li Sun; Shi-Lei Tang; Noreen J. Evans; Zhao-Feng Zhang; Li-Yun Zhang; Fu-Long Cai; Wei-Ming Fan; Lin Ding (Lithos, 2025)

Formation of amino acid–based imidazole salts considerably increased the determined level of fluorescent advanced glycation end products in biscuits - Yuanyuan Liu; Yufeng Liang; Ruixia Qiu; Caihuan Huang; Jie Zheng; Fu Liu; Shiyi Ou; Juanying Ou (Food Chemistry, 2025)

New evidence for the involvement of superoxide and singlet oxygen in UV-activated peroxydisulfate system under acidic conditions - Pu Wang; Lingli Wang; Ronghui Xiao; Sifan Qiu; Jinhui Cao; Yu Fu; Zhaohui Wang (Chemical Engineering Journal, 2025)

Redox-copolymer-enhanced electrochemical catalysis membrane for efficient water decontamination - Zhen Qiu; Cheng Chen; Xin Zeng; Guanda Shen; Qisheng Ye; Hailu Fu; Yongfu Li; Bing Yu (Chemical Engineering Journal, 2025)

Underground laboratories · Deep underground observation · Scientific questions—Insights from observations of multi-physic fields in deep underground labs - Huiqi Ren; Yun Wang; Chang Chen; Guangyu Fu; Longqing Qiu; Lianghui Guo; Chengliang Xie; Yongsheng He; Heping Sun; Jiwen Teng (Science China Earth Sciences, 2025)

Impacts of continuous potato cropping on soil microbial assembly processes and spread of potato common scab - Lichun Wang; Song Liu; Guokui Tian; Yang Pan; Haiyan Wang; Guangwei Qiu; Fengyun Li; Ze Pang; Kaixin Ding; Jinpeng Zhang; Hong Xue; Xinyuan Li; et al. (Applied Soil Ecology, 2025)

Mechanism of selenium-enriched Bacillus subtilis alleviating perfluorohexanoic acid toxicity in Carassius auratus through the microbiota–gut–brain axis - Xue Jiao; Faye Zhang; Lei Guo; Zheng-Yao Guo; Qiu-Shuang Fu; Cheng-Cheng Bi; Xian-Wei Hou; Ning Wang; Jing-Xiang Zhou; Yue-Hong Li (Aquaculture, 2025)

Inhibition under cold storage can accelerate the realization of stable partial nitrification - Yihao Bian; Kunming Fu; Teng Guan; Aotong Huo; Ruibao Zhang; Xueqin Li; Wenbing Yang; Xiaodan Li; Zirui Li; Fuguo Qiu (Chemical Engineering Journal, 2025)

Fully Coupled Thermo-hydro-mechanical Model for Wellbore Stability Analysis in Deep Gas-Bearing Unsaturated Formations Based on Thermodynamics - Tianshou Ma; Jinhua Liu; Jianhong Fu; Yi Qiu; Xiangyu Fan; Dmitriy A. Martyushev (Rock Mechanics and Rock Engineering, 2025)

An ultra-sensitive SERS approach by electrostatic enrichment of charged analytes on Ag/laponite nanocomposites - Hao Zhang; Chaopeng Fu; Jianhao Ding; Guoqiang Xu; Chunhui Zhou; Zhenyu He; Zhimin Ou; Dongshen Tong; Minyang Qiu; Xiangdong Zhou; Xiaonian Li (Applied Clay Science, 2025)

Genomic Architecture Underlying the Striking Colour Variation in the Presence of Gene Flow for the Guinan Toad‐Headed Lizard - Ying Chen; Song Tan; Qiwei Xu; Jinzhong Fu; Yin Qi; Xia Qiu; Weizhao Yang (Molecular Ecology, 2025)
How divergence occurs between closely related organisms in the absence of geographic barriers to gene flow stands as one of the long‐standing questions in evolutionary biology. Previous studies suggested that the interplay between selection, gene flow and recombination strongly affected the process of divergence with gene flow. However, the extent to which these forces interact to drive divergence remains largely ambiguous. Guinan toad‐headed lizards ( Phrynocephalus guinanensis ) in the Mugetan Desert exhibit striking colour differences from lizards outside the desert and provide an excellent model to address this question. Through extensive sampling and whole genome sequencing, we obtained genotypes for 191 samples from 14 populations inside and outside the desert. Despite the colour differences, continuous and asymmetric gene flow was detected across the desert border. More importantly, 273 highly diverged regions (HDRs) were identified between them, accounting only for 0.47% of the genome but widely distributed across 20 (out of the total 24) chromosomes. Strong signatures of selection were identified in HDRs, and local recombination rates were repressed. Furthermore, five HDRs exhibited significantly higher divergence, which contained key genes associated with crucial functions in animal coloration, including pteridine and melanocyte pigmentation. Genes related to retinal cells and steroid hormones were identified in other HDRs, which might have also contributed to the formation of colour variation in the presence of gene flow. This study provided novel insights into the understanding of the evolutionary mechanisms of genetic divergence in the presence of gene flow.

Candidatus Thiothrix phosphatis SCUT-1: A novel polyphosphate-accumulating organism abundant in the enhanced biological phosphorus removal system - Liping Chen; Xuhan Deng; Xiaojing Xie; Kaiying Wang; Hang Chen; Sheqi Cen; Fu Huang; Cenchao Wang; Yaqian Li; Chaohai Wei; Guanglei Qiu (Water Research, 2024)

Driving factor, source identification, and health risk of PFAS contamination in groundwater based on the self-organizing map - Jingwen Zeng; Kai Liu; Xiao Liu; Zhongen Tang; Xiujuan Wang; Renchuan Fu; Xiaojun Lin; Na Liu; Jinrong Qiu (Water Research, 2024)

Nano titanium dioxide induces HaCaT cell pyroptosis via regulating the NLRP3/caspase-1/GSDMD pathway - Wanting Fu; Mingxue Liu; Yu Wang; Huimin Yang; Aoqi Ye; Jianhong Wu; Yang Li; Zejun Yu; Yinsheng Qiu; Lingyun Xu (Toxicology Letters, 2024)

Distinct accumulation patterns, translocation efficiencies, and impacts of nano-fertilizer and nano-pesticide in wheat through foliar versus soil application - Erkai He; Xing Li; Xueqing Xu; Zhuozhong Fu; Ana Romero-Freire; Hao Qiu (Journal of Hazardous Materials, 2024)

Migration of heavy metals in soil-plant system after land use of sewage sludge at high application ratio - Huan Wang; Qian Chen; Fenfen Zhu; Jiawei Wang; Bing Zhao; Xingmin Fu; Yuqun Qiu; Renhua Chen (Journal of Hazardous Materials, 2024)

N6-methyladenosine demethylase FTO regulates neuronal oxidative stress via YTHDC1-ATF3 axis in arsenic-induced cognitive dysfunction - Lixiao Zhou; Renjie Li; Fu Wang; Ruiqi Zhou; Yinyin Xia; Xuejun Jiang; Shuqun Cheng; Fanghong Wang; Danyang Li; Jun Zhang; Lejiao Mao; Xuemei Cai; et al. (Journal of Hazardous Materials, 2024)

Fluorescence imaging of dopamine in living cells triggered by unique coupling reactions - Shaofei Fu; Jianwen Qiu; Biaofeng Gu; Yong Gao (Analytica Chimica Acta, 2024)

Contrast and Genomic Characterisation of Ancient and Recent Interspecific Introgression Between Deeply Diverged Moustache Toads ( Leptobrachium ) - Jun Li; Qingbo Ai; Siyu Xie; Chunhua Huang; Fuyuan Qiu; Chao Fu; Mian Zhao; Jinzhong Fu; Hua Wu (Molecular Ecology, 2024)
Recent genomic analyses have provided new insights into the process of interspecific introgression and its consequences on species evolution. Most recent studies, however, focused on hybridization between recently radiated species, with few examining the genomic outcomes of ancient hybridization across deeply diverged species. Using whole genome data of moustache toads ( Leptobrachium ), we identified signals of three hybridization events among nine species that diverged at the Eocene. An ancient introgression from L. leishanense to the ancestral branch (C1) of L. liui introduced adaptive variants. The highly introgressed regions include genes with important functions in odorant detection and immune responses. These genes are preserved in all three descendent populations of L. liui _C1, and these regions likely have been positively selected over a long filtering process. A recent introgression occurred from L. huashen to L. tengchongense , with the introgressed regions being mostly neutral. Furthermore, one F1 hybrid individual was detected between sympatric L. ailaonicum and L. promustache . The signals of introgression largely disappeared after removing the hybrid individual, indicating an occasional hybridization but minimal introgression. Further examination of highly divergent but low introgressed genomic regions revealed both pre‐mating isolation and genetic incompatibility as potential mechanisms of resisting introgression and maintaining species boundaries. Additionally, no large X‐effect was found in these introgression events. Hybridization between deeply diverged amphibian species may be common, but detectable introgressions are likely less so, with recent introgression being mostly neutral and the rare ancient one potentially adaptive. Our findings complement recent genomic work, and together they provide a better understanding of the genomic characteristics of interspecific introgression and its significance in species adaptation and evolution.

A recombinant pseudorabies virus surface - displaying the classical swine fever E2 protein induces specific antibodies rapidly - Xinyu Zhang; Hongxia Wu; Tianqi Gao; Yongfeng Li; Dailang Zhong; Mingzhi Li; Shuwen Li; Caoyuan Ma; Assad Moon; Qiang Fu; Hua-Ji Qiu; Yuan Sun (Veterinary Microbiology, 2024)

Research on dynamic response characteristics of red clay low embankment with different road structures under vehicle load - Jinhong Li; Hongyuan Fu; Xiang Qiu; Yong Wu; Jingchen Chen (Transportation Geotechnics, 2024)

The influence of sand content on dynamic behaviors of ballast bed from a multiscale perspective - Shuchen Wang; Longlong Fu; Haonan Xi; Yongjia Qiu; Shunhua Zhou (Transportation Geotechnics, 2024)

Rapid and extensive SARS-CoV-2 Omicron variant infection wave revealed by wastewater surveillance in Shenzhen following the lifting of a strict COVID-19 strategy - Yinghui Li; Chen Du; Ziquan Lv; Fuxiang Wang; Liping Zhou; Yuejing Peng; Wending Li; Yulin Fu; Jiangteng Song; Chunyan Jia; Xin Zhang; Mujun Liu; et al. (Science of The Total Environment, 2024)

Construction S-scheme Bi4O5Br2/BiOI composite for accelerated charge separation and enhanced photocatalytic degradation and antibacterial performance - Liying Huang; Li Qiu; Yanling Li; Heman Xie; Menghao Zhu; Shuai Liu; Yanyan Fu; Jun Huang; Yeping Li; Lijing Huang (Process Safety and Environmental Protection, 2024)

S-scheme 2D/2D B-doped N-deficient g-C3N4/ZnIn2S4 heterojunction for efficient H2 production intergrated with tertracycline degradation under visible-light illumination - Jiajia Liu; Yaodi Fu; Guoliang Chu; Ke Wen; Lingfang Qiu; Ping Li; Lihong Cheng; Banpeng Cao; Yi Tang; Xiangshu Chen; Hidetoshi Kita; Shuwang Duo (Process Safety and Environmental Protection, 2024)

Indicative impacts of sludge properties and biological metabolic characteristics on high-rate contact stabilization process performance - Zhongqi Jiang; Mengxuan Deng; Shan Qiu; Mengqi Fu; Mu Yuan; Qinxue Wen; Xinghua Jia (Journal of Environmental Management, 2024)

Blood mercury mediates the associations between fish consumption and serum uric acid levels among Chinese adults: A nationally representative study - Changzi Wu; Bing Wu; Yingli Qu; Hui Fu; Yue Chen; Yifu Lu; Saisai Ji; Liang Ding; Zheng Li; Qi Sun; Miao Zhang; Xu Zhang; et al. (Environmental Research, 2024)

Efficient peroxymonosulfate activation for practical wastewater treatment by Biochar-Iron oxide composite-based hydrogel beads - Zefeng Ruan; Ronghao Wu; Cheng Fu; Hailu Fu; Hai Xiang; Yongfu Li; Zhen Qiu; Bing Yu (Chemical Engineering Journal, 2024)

A point-of-care testing strip based on a rationally designed antigen and antibody for fast and reliable Diquat poisoning detection: Ready for clinical application - Shun Zhang; Guanyan Fu; Weijing Yi; Jiahui Zhou; Wenbin Liang; Wanjiang Zhao; Tian Zhang; Gen Zhang; Jing Zhang; Huiling Li; Huifang Yan; Banghua Wu; et al. (Chemical Engineering Journal, 2024)

Study on the integrated technology of arsenic removal and tungsten extraction based on the formation and decomposition of arsenotungstic acid - Caifang Cao; Ailin Fu; Qiuxian Mai; Yong Li; Huaping Nie; Jian Wang; Dandan Gong; Xiaochen Qiu (Chemical Engineering Journal, 2024)

Effects of tourmaline on the establishment, idling, and recovery of partial nitrification: Mechanistic understanding and performance evaluation - Mu Yuan; Xiaohan Jiang; Baojian Jing; Jue Wang; Mengqi Fu; Mengxuan Deng; Shuoqi Ren; Zhongqi Jiang; Fengxia Deng; Shan Qiu (Chemical Engineering Journal, 2024)

Marsh decrease was much faster than the water increase among the Yellow River Source wetlands during 1986–2022 - Mengqi Qiu; Yanxu Liu; Fuyou Tian; Shuai Wang; Bojie Fu (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Soil and stone terraces offset the negative impacts of sloping cultivation on soil microbial diversity and functioning by protecting soil carbon - Yingbo Qiu; Qi Fu; Yihang Yang; Jiayi Zhao; Jiaxin Li; Fan Yi; Xianheng Fu; Yu Huang; Zhengchao Tian; Joshua L. Heitman; Zhiyuan Yao; Zhongmin Dai; et al. (Journal of Environmental Management, 2024)

New insight into catalytic performance and reaction mechanism for butyl acetate over CeO2 catalysts: Oxygen vacancy and surface reactive oxygen species - Jiajia Lin; Wenjing Kong; Chuying Qiu; Xueyun Zhong; Yanjun Li; Mingli Fu; Zhenguo Li (Journal of Environmental Chemical Engineering, 2024)

Characterization and immune role of class B scavenger receptor member 1 in spotted sea bass (Lateolabrax maculatus) - Yichen Fu; Chao Zhao; Changhong Lin; Bo Zhang; Lulu Yan; Bo Zhang; Pengfei Wang; Lihua Qiu (Fish & Shellfish Immunology, 2024)

Ionic liquid-derived carbon dots with enhanced antibacterial activity and antibiofilm capability for treatment of MRSA-infected wounds - Chenxi Gao; Xiaoqing Qu; Lei Fu; Jia Chen; Yuefeng Chu; Hongdeng Qiu (Chemical Engineering Journal, 2024)

Anti-Z-scheme polymer/polymer heterojunctions achieving synchronous enhancement of light absorption and directly spatial charge separation - Yong Li; Xinjia Zhang; Jianhua Zheng; Tianyuan Xiao; Qiu Fu; Can Yang; Dongting Wang; Guoqiang Zhang (Chemical Engineering Journal, 2024)

Identification of transcription factor BnHDG4-A08 as a novel candidate associated with the accumulation of oleic, linoleic, linolenic, and erucic acid in Brassica napus - Ying Fu; Min Yao; Ping Qiu; Maolin Song; Xiyuan Ni; Erli Niu; Jianghua Shi; Tanliu Wang; Yaofeng Zhang; Huasheng Yu; Lunwen Qian (Theoretical and Applied Genetics, 2024)

Ancestral sequence reconstruction of the prokaryotic three-domain laccases for efficiently degrading polyethylene - Bo Zeng; Yishan Fu; Jiacai Ye; Penghui Yang; Shixiu Cui; Wenxuan Qiu; Yangyang Li; Taoxu Wu; Haiyun Zhang; Yachan Wang; Guocheng Du; Song Liu (Journal of Hazardous Materials, 2024)

Self-hydrogen transfer hydrogenolysis of β-O-4 bonds in lignin model compounds over NiCu/Al2O3 catalyst - Fa-Peng Wu; Le-Le Qiu; Yun-Peng Zhao; Zong-Pin Fu; Jing Liang; Jian Xiao; Jian Li; Fang-Jing Liu; Jing-Pei Cao (Fuel, 2024)

The co-assembly of spike silica nanoparticles with high affinity to nucleic acid for airborne virus detection - Xue Zhang; Yamin Yu; Kaixin Du; Wenwei Han; Jie Xue; Shanshan Li; Shangyou Lv; Jianye Fu; Xin Wang; Meng Qiu (Chemical Engineering Journal, 2024)

Ferrocenedicarboxylate modified Bi-MOF for water decontamination via different advanced oxidation processes: Multifunction, mechanisms and biotoxicity test - Ya Gao; Fei Wang; Jie Tang; Chong-Chen Wang; Xiao-Hong Yi; Yuwei Wei; Guangchi Liu; Peng Wang; Huifen Fu; Chen Zhao; Xuchun Qiu; Shouliang Yi (Chemical Engineering Journal, 2024)

Liriodendrin stimulates proliferation and milk protein synthesis of mammary epithelial cells via the PI3K-DDX18 signaling - Youwen Qiu; Mingming Fu; Minghui Zhang; Bo Qu; Zhen Zhen (In Vitro Cellular & Developmental Biology - Animal, 2024)

Physiological and behavioral responses to social isolation and starvation in a social fish - Dan-Dan Xu; Chun-Hua Wang; Jin-Qiu Bi; Huan Luo; Shi-Jian Fu; Bin Li; Ling-Qing Zeng (Applied Animal Behaviour Science, 2024)

Relating the carbon sources to denitrifying community in full-scale wastewater treatment plants - Jinling Chen; Xia Tang; Xuewei Wu; Biping Li; Xia Tang; Xueran Lin; Pengfei Li; Hang Chen; Fu Huang; Xuhan Deng; Xiaojing Xie; Chaohai Wei; et al. (Chemosphere, 2024)

Advanced strategies for conversing and fixing sulfur during waste resins oxidation through Ca/Zn oxides enhanced Na2CO3-K2CO3 system - Xin Liu; Yong-De Yan; Yun Xue; Yang-Hai Zheng; Jing-Ping Wang; Qing-Guo Zhang; Yue-Lin Wang; Fu-Qiu Ma (Process Safety and Environmental Protection, 2024)

Molecular-level insight into the origin-dependent adsorption fractionation of dissolved organic matter on ferrihydrite in aquatic environment: Implications for carbon sink in eutrophic lakes - Chengyu Suo; Wensi Zhao; Shasha Liu; Rui Fu; Yi Ren; Yue Qiu; Yuxin Zhang; Zhongqi He; Baoshan Xing; Fengchang Wu (Chemical Engineering Journal, 2024)

Flow pattern and pressure loss of foam flow in horizontal pipes: Role of surfactant type and dynamic surface tension - Huan Li; Zhihao Fu; Xiaoyang Yu; Yuqing Song; Ke Qiu; Shouxiang Lu (Chemical Engineering Journal, 2024)

Effects of agricultural mulch film on swine manure composting: Film degradation and nitrogen transformation - Zhiqiang Chen; Jie Ren; Zerui Yun; Qinxue Wen; Qiqi Fu; Shan Qiu (Bioresource Technology, 2024)

Mechanisms and high-value applications of phthalate isomers degradation pathways in bacteria - Qiu Lequan; Fu Yanan; Zhou Xianda; Bao Mengyuan; Li Chenyu; Wu Shijin (World Journal of Microbiology and Biotechnology, 2024)

High dimensional proteomic mapping of bone marrow immune characteristics in immune thrombocytopenia - Feng-Qi Liu; Qing-Yuan Qu; Ying Lei; Qi Chen; Yu-Xiu Chen; Meng-Lin Li; Xue-Yan Sun; Ye-Jun Wu; Qiu-Sha Huang; Hai-Xia Fu; Yuan Kong; Yue-Ying Li; et al. (Science China Life Sciences, 2024)

Role of ginsenoside Rb1 in attenuating depression-like symptoms through astrocytic and microglial complement C3 pathway - Cheng-Fu Li; Qiu-Ping Zhang; Jie Cheng; Guang-Hui Xu; Ji-Xiao Zhu; Li-Tao Yi (Metabolic Brain Disease, 2024)

The emerging and legacy persistent organic contaminants in corals of the South China Sea - Yao-Wen Qiu; Jun Li; Mei-Xia Zhao; Ke-Fu Yu; Gan Zhang (Chemosphere, 2024)

Hydrochemical and microbial community characteristics and the sources of inorganic nitrogen in groundwater from different aquifers in Zhanjiang, Guangdong Province, China - Rentao Liu; Jinrong Qiu; Shuang Wang; Renchuan Fu; Xiaochen Qi; Chuanqi Jian; Qizhi Hu; Jingwen Zeng; Na Liu (Environmental Research, 2024)

Bifunctional pyridinium-based Brønsted acidic porous ionic liquid for deep oxidative desulfurization - Jie Yin; Wendi Fu; Jinrui Zhang; Xinmiao Zhang; Wenxiang Qiu; Wei Jiang; Linhua Zhu; Hongping Li; Huaming Li (Chemical Engineering Journal, 2024)

Deep soil microbial carbon use efficiency responds stronger to nitrogen deposition than top soil in tropical forests, southern China - Yamin Jiang; Tianyan Su; Huafeng Wang; Qiu Yang; Jingli Lu; Qunyou Fu; Han Mao; Wenxian Xu; Yiqi Luo; Wenjie Liu; Huai Yang; Mengyang Fang (Plant and Soil, 2024)

A novel fluorescence platform for specific detection of tetracycline antibiotics based on [MQDA-Eu3+] system - Jia-Mei Ran; Liu Yang; Chun-Tong Liu; Qiu-Huan Liu; Yu-Long Liu; Shi-Jie Li; Ying Fu; Fei Ye (Science of The Total Environment, 2024)

Biochar dose-dependent impacts on soil bacterial and fungal diversity across the globe - Jiayi Zhao; Yingbo Qiu; Fan Yi; Jiaxin Li; Xueying Wang; Qi Fu; Xianheng Fu; Zhiyuan Yao; Zhongmin Dai; Yunpeng Qiu; Huaihai Chen (Science of The Total Environment, 2024)

Turbulent transports in the flow around a rectangular cylinder with different aspect ratios - Jiang-hua Li; Bo-fu Wang; Xiang Qiu; Quan Zhou; Shi-xiao Fu; Yu-lu Liu (Ocean Engineering, 2024)

Effect of different dissolved oxygen enrichment incubation conditions on the realization of partial nitrification under microaerobic condition - Yihao Bian; Kunming Fu; Wenbing Yang; Jia Kang; Zirui Li; Xiaodan Li; Haoxin Xi; Fuguo Qiu (Journal of Water Process Engineering, 2024)

ZnO enhanced molten Na2CO3-K2CO3 system for simulated waste resins treatment: Efficient conversion and fixation of organic sulfur and iron(III) - Xin Liu; Yong-De Yan; Yun Xue; Yang-Hai Zheng; Yue-Lin Wang; Jing-Ping Wang; Fu-Qiu Ma (Journal of Environmental Chemical Engineering, 2024)

CXCL1/IGHG1 signaling enhances crosstalk between tumor cells and tumor-associated macrophages to promote MC-LR-induced colorectal cancer progression - Lingqiao Wang; Weiyan Chen; Huidong Jin; Yao Tan; Chengwei Guo; Wenjuan Fu; Zhiling Wu; Ke Cui; Yiqi Wang; Zhiqun Qiu; Guowei Zhang; Wenbin Liu; et al. (Environmental Pollution, 2024)

Pearl-inspired self-extinguishing, thermal-conductive, and robust thermoplastic polyurethane composite by strengthening inter-layer packing - Yongbin Wang; Kaichao Pan; Yong Fan; Yifeng Fu; Jieying Tu; Weiqiang Zhao; Wenjin Guo; Zunfeng Liu; Jun Qiu (Chemical Engineering Journal, 2024)

Proposal and application of a novel isothermal model for the thermodynamic study of ion exchange reactions - Caifang Cao; Yong Li; Ailin Fu; Gengfeng Deng; Xiaowen Li; Yupeng Li; Xiaochen Qiu (Chemical Engineering Journal, 2024)

Draconibacterium aestuarii sp.nov., a Glycolipid-Producing Bacterium Isolated from Tidal Flat Sediment and Emended Description of the Genus Draconibacterium - Jia-Yan Wang; Sha-Sha Qiu; Yue Su; Wei-Yu Pan; Tao Wang; Wen-Wu Zhang; Ge-Yi Fu; Min Wu (Current Microbiology, 2024)

E3 Ubiquitin Ligase ASB14 Inhibits Cardiomyocyte Proliferation by Regulating MAPRE2 Ubiquitination - Yanpeng Yang; Dongpu Ma; Bo Liu; Xu Sun; Wei Fu; Feifei Lv; Chunguang Qiu (Cell Biochemistry and Biophysics, 2024)

Damage constitutive model for soft rocks and its experimental verification on silty mudstone considering cyclic rock‒water interactions - Xiao-Wei Yu; Hong-Yuan Fu; Ling Zeng; Jie Liu; Xing-Yu Qiu (Bulletin of Engineering Geology and the Environment, 2024)

Coupling Coordination Analysis of Cropland Intensification and Agroecosystem Services: Evidence from Loess Plateau in Shaanxi Province, China - Shaowu Fu; Mengyu Fu; Menglong Qiu (Chinese Geographical Science, 2024)

Soil microbial community variation in vanadium-enriched farmland surrounding vanadium titanomagnetite tailing in Southwest China - Yunxia Fu; Mingxing Li; Jianpeng Li; Dilin Chen; Tianhui Ye; Can Wang; Fangfang Yan; Zhongping Qiu (Applied Soil Ecology, 2024)

Shared xerophytic genes and their re‐use in local adaptation to aridity in the desert plant Gymnocarpos przewalskii - Ruirui Fu; Yuxiang Zhu; Ying Liu; Zhaoping Yang; Ruisen Lu; Yingxiong Qiu; Martin Lascoux; Pan Li; Jun Chen (Molecular Ecology, 2024)
In order to thrive and survive, plant species need to combine stability in the long term and rapid response to environmental challenges in the short term. The former would be reflected by parallel or convergent adaptation across species, and the latter by pronounced local adaptation among populations of the same species. In the present study, we generated a high‐quality genome and re‐sequenced 177 individuals for Gymnocarpos przewalskii , an important desert plant species from North‐West China, to detect local adaptation. We first focus on ancient adaptation to aridity at the molecular level by comparing the genomic data of 15 species that vary in their ability to withstand aridity. We found that a total of 118 genes were shared across xerophytic species but absent from non‐xerophytic species. Of the 65 found in G. przewalskii , 63 were under purifying selection and two under positive selection. We then focused on local adaptation. Up to 20% of the G. przewalskii genome showed signatures of local adaptation to aridity during population divergence. Thirteen of the selected shared xerophytic genes were reused in local adaptation after population differentiation. Hence, only about 20% of the genes shared and specific to xerophytic species and associated with adaptation to aridity were later recruited for local adaptation in G. przewalskii .

Phosphate-mediated degradation of organic pollutants in water with peroxymonosulfate revisited: Radical or non-radical oxidation? - Lingli Wang; Qingchao Li; Chunxiao Xu; Yu Fu; Yi Tang; Pu Wang; Zhen Zhang; Yuqi Xia; Xiaojing Liu; Jinhui Cao; Sifan Qiu; Yanna Xue; et al. (Water Research, 2024)

Research on optimization strategy of TBM tunneling parameters based on stratum perception and simulation tunneling experiment - Kang Fu; Daohong Qiu; Yiguo Xue; Yufan Tao; Fanmeng Kong (Tunnelling and Underground Space Technology, 2024)

Using network pharmacology and molecular docking to uncover the mechanism by which quercetin alleviates deoxynivalenol-induced porcine intestinal injury - Pu Guo; Xuemin Li; Yunda Xue; Qirong Lu; Yu Liu; Jianglin Xiong; Zhongyuan Wu; Shulin Fu; Chun Ye; Xu Wang; Yinsheng Qiu (Toxicon, 2024)

The Cambrian microfossil Qingjiangonema reveals the co-evolution of sulfate-reducing bacteria and the oxygenation of Earth’s surface - Linhao Cui; Kelei Zhu; Ruiyun Li; Chao Chang; Laiyuan Wu; Wei Liu; Dongjing Fu; Peiyu Liu; Hao Qiu; Guoqiang Tang; Qiuli Li; Robert R. Gaines; et al. (Science Bulletin, 2024)

Hydroclimate variability over the past 4730 years based on multi-proxy stalagmite records from southwest China - Kui Gao; Yaoqi He; Yan Yang; Xiuyang Jiang; Xin Fu; Tanui Moses Kipkorir; Wanyin Qiu; Yi Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Selenium protects against Pb-induced renal oxidative injury in weaning rats and human renal tubular epithelial cells through activating NRF2 - Chongmei Tian; Yu Qiu; Yaping Zhao; Liping Fu; Daozong Xia; Junjie Ying (Journal of Trace Elements in Medicine and Biology, 2024)

A comprehensive review of biodetoxification of trichothecenes: Mechanisms, limitations and novel strategies - Yue Qiu; Jiaping Yan; Aodong Yue; Zhongchao Lu; Jianzhuang Tan; Hong Guo; Yuting Ding; Fei Lyu; Yan Fu (Food Research International, 2024)

Fabrication of starch-based oleogels using capillary bridges: Potential for application as edible inks in 3D food printing - Wenbo Miao; Yijie Fu; Zhiheng Zhang; Qianzhu Lin; Xiaojing Li; Shangyuan Sang; David Julian McClements; Han Jiang; Hangyan Ji; Chao Qiu; Zhengyu Jin (Food Hydrocolloids, 2024)

Full-spectrum-responsive Ti4O7-PVA nanocomposite hydrogel with ultrahigh evaporation rate for efficient solar steam generation - Xinye Xu; Qi Zhao; Qi Liu; Junxiao Qiu; Jinhao Li; Wenqian Zheng; Jie Cao; Lina Wang; Wen Wang; Shutong Yuan; Anni Fu; Hanjun Yang; et al. (Desalination, 2024)

Environmental concentrations of acetaminophen and its metabolites promote the spread of antibiotic resistance genes through pheromone signaling pathway - Xinyue Fu; Xiaobo Yang; Xiaoli Lin; Li Zhu; Panpan Yang; Feng Wang; Zhiqiang Shen; Jingfeng Wang; Yun Ling; Zhigang Qiu (Chemical Engineering Journal, 2024)

Model predictive control for automatic operation of space nuclear reactors: Design, simulation, and performance evaluation - Jianghan Fu; Zhao Jin; Zhiwen Dai; G.H. Su; Chenglong Wang; Wenxi Tian; Suizheng Qiu (Annals of Nuclear Energy, 2024)

Diterpenoid alkaloids with chemotaxonomic significance from Aconitum polycarpum - Lin Chen; Jie Wen; Jia-Yi Ma; Ke Xu; Cheng-En Fu; Wen-Cheng Liang; Chen-Ying Zhu; Jin-Qiu Wang; Shuai Huang; Xian-Li Zhou (Biochemical Systematics and Ecology, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Expression of ethylene biosynthetic genes during flower senescence and in response to ethephon and silver nitrate treatments in Osmanthus fragrans - Hui Qiu; Yiwen Chen; Jianxin Fu; Chao Zhang (Genes & Genomics, 2024)

Characterizing the regional variation of ballast particles’ movement during the increase of local void in ballast bed - Haonan Xi; Longlong Fu; Shuchen Wang; Yongjia Qiu; Shunhua Zhou; Binglong Wang (Transportation Geotechnics, 2024)

Effects of intensive chlorine disinfection on nitrogen and phosphorus removal in WWTPs - Yixing Zhang; Xueran Lin; Tang Xia; Hang Chen; Fu Huang; Chaohai Wei; Guanglei Qiu (Science of The Total Environment, 2024)

High-performance plastic-derived metal-free catalysts for organic pollutants degradation via Fenton-like reaction - Yu Hou; Qi Fu; Huajie Zhong; Jiaxing Yu; Yuan Tao; Zeyu Gong; Jianqiang Li; Songbo Wei; Junlang Qiu; Junhui Wang; Fang Zhu; Gangfeng Ouyang (Science of The Total Environment, 2024)

Tourmaline mediated enhanced autotrophic denitrification: The mechanisms of electron transfer and Paracoccus enrichment - Mengqi Fu; Shan Qiu; Jue Wang; Yingshi Zhu; Mu Yuan; Liang Wang (Science of The Total Environment, 2024)

Waveguide invariant distribution estimation using autoregressive - Discrete Fourier transform and its application in source depth classification - Jin Fu; Yixin Miao; Nan Zou; Longhao Qiu; Wenbo Zhu (Ocean Engineering, 2024)

Timing of India-Asia suturing: Evidence from a remnant peripheral foreland basin in Xigaze, South Tibet - Xu-Dong Guo; Lin Ding; Qiu-yun Guan; Deng Zeng; Chao Wang; Gui-zhen Guo; Hou-Qi Wang; Mei-Yu Liu; Xiang-Li Ding; Muhammad Qasim; Ya-Hui Yue; Jing Xie; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Bio-based ionic liquid filter with enhanced electrostatic attraction for outside filtration and inside collection of viral aerosols - Guo-Hao Zhang; Qiu-Hong Zhu; Lei Zhang; Lei Li; Jie Fu; Shuang-Long Wang; Wen-Li Yuan; Ling He; Guo-Hong Tao (Journal of Hazardous Materials, 2024)

Devonian stratiform ironstone deposits in South China formed in a shallow marine environment of a passive continental margin - Mei-Fu Zhou; Yuanjun Jonathan Lyu; Zerui Ray Liu; Ping-Ping Liu; Lei Meng; Wenhong Johnson Qiu; Wen Winston Zhao (Journal of Asian Earth Sciences, 2024)

Genomic and epigenetic characterization of the arsenic-induced oncogenic microRNA-21 - Haoyan Ji; Zhuoyue Bi; Aashna S. Pawar; Akimasa Seno; Bandar Saeed Almutairy; Yao Fu; Yiran Qiu; Wenxuan Zhang; Ziwei Wang; Chitra Thakur; Hongjuan Cui; Liqun Yang; et al. (Environmental Pollution, 2024)

Contrasting range changes of Bergenia (Saxifragaceae) species under future climate change in the Himalaya and Hengduan Mountains Region - Li Qiu; Qing-Li Fu; Hans Jacquemyn; Kevin S. Burgess; Jia-Jing Cheng; Zhi-Qiong Mo; Xiao-Dong Tang; Bo-Yun Yang; Shao-Lin Tan (Theoretical and Applied Climatology, 2024)

Larger hydroxyapatite aggregation from Ca2+ adhesion in ANAMMOX granular sludge caused by high dissolved oxygen - Mu Yuan; Shan Qiu; Mengqi Fu; Mengxuan Deng; Jue Wang; Fengxia Deng (Chemosphere, 2024)

Short-term effects of exposure to ambient PM2.5 and its components on hospital admissions for threatened and spontaneous abortions: A multicity case-crossover study in China - Heng He; Na Wan; Zhenzhen Li; Zihan Zhang; Zesen Gao; Qingdan Liu; Xiaolei Ma; Yuqing Zhang; Rongxiang Li; Xiuhong Fu; Weihong Qiu (Chemosphere, 2024)

Baicalin attenuates lipopolysaccharide-induced intestinal inflammatory injury via suppressing PARP1-mediated NF-κB and NLRP3 signalling pathway - Qirong Lu; Nan Wang; Defeng Wen; Pu Guo; Yu Liu; Shulin Fu; Chun Ye; Zhongyuan Wu; Yinsheng Qiu (Toxicon, 2024)

Impact of antioxidants on PM2.5 oxidative potential, radical level, and cytotoxicity - Yixiang Wang; Chunbo Xing; Baohua Cai; Wenhui Qiu; Jinghao Zhai; Yaling Zeng; Antai Zhang; Shao Shi; Yujie Zhang; Xin Yang; Tzung-May Fu; Huizhong Shen; et al. (Science of The Total Environment, 2024)

Monotonic trends of soil microbiomes, metagenomic and metabolomic functioning across ecosystems along water gradients in the Altai region, northwestern China - Qi Fu; Yingbo Qiu; Jiayi Zhao; Jiaxin Li; Siqi Xie; Qiuchang Liao; Xianheng Fu; Yu Huang; Zhiyuan Yao; Zhongmin Dai; Yunpeng Qiu; Yuchun Yang; et al. (Science of The Total Environment, 2024)

Effects of simulated warming on soil microbial community diversity and composition across diverse ecosystems - Jiayi Zhao; Xuan Xie; Yuying Jiang; Jiaxin Li; Qi Fu; Yingbo Qiu; Xianheng Fu; Zhiyuan Yao; Zhongmin Dai; Yunpeng Qiu; Huaihai Chen (Science of The Total Environment, 2024)

Green synthesis of CaxLa1-xMnO3 with modulation of mesoporous and vacancies for efficient low concentration phosphate adsorption - Menghan Feng; Mengmeng Li; Changbin Guo; Mingyao Yuan; Lisheng Zhang; Shangkai Qiu; Weilin Fu; Keqiang Zhang; Haixin Guo; Feng Wang (Journal of Environmental Management, 2024)

Soil carbon turnover and balance in the priming effects of basalt, montmorillonite, and kaolinite in a Luvisol soil - Junyan Xu; Junli Liu; Qinglin Fu; Ming Zhang; Bin Guo; Hua Li; Xiaodong Chen; Gaoyang Qiu (Journal of Soils and Sediments, 2024)

Wheat cultivar replacement drives soil microbiome and microbial cooccurrence patterns - Jie Lu; Xiaogang Yin; Kangcheng Qiu; Robert M. Rees; Matthew Tom Harrison; Fu Chen; Xinya Wen (Agriculture, Ecosystems & Environment, 2024)

Specific gut bacterial taxa inhabited in healthy shrimp (Penaeus vannamei) confer protection against Vibrio parahaemolyticus challenge - Xuezhi Fu; Jikun He; Jing Wang; Fengguang Shen; Jiayi Qiu; Chen Chen; Demin Zhang; Haipeng Guo (Aquaculture, 2024)

Integrating network pharmacology and experimental validation to explore the mechanisms of luteolin in alleviating fumonisin B1–induced intestinal inflammatory injury - Defeng Wen; Wantong Han; Quan Chen; Guanhui Qi; Mengling Gao; Pu Guo; Yu Liu; Zhongyuan Wu; Shulin Fu; Qirong Lu; Yinsheng Qiu (Toxicon, 2024)

Concentration identification and endpoint-oriented health risk assessments on a broad-spectrum of organic compounds in atmospheric fine particles: A sampling experimental study in Beijing, China - Ke Gao; Linxiao Wang; Yifan Xu; Yidan Zhang; Haonan Li; Jie Fu; Jianjie Fu; Liping Lu; Xinghua Qiu; Tong Zhu (Science of The Total Environment, 2024)

Dynamic analysis and design of novel distributed lump-parameters mounting system for marine power devices - Yuanran Qiu; Wei Xu; Junqiang Fu; Zechao Hu; Guanghui Cheng (Ocean Engineering, 2024)

Study on photofluorescent uranium ore sorting based on deep learning - Jun Qiu; Yan Zhang; Chunqing Fu; Yuchao Yang; Yujin Ye; Renbo Wang; Bin Tang (Minerals Engineering, 2024)

Garnet geochemistry reveals late-stage oxidation of tin-bearing fractionated granite - Jin-Xiang Li; Lin Ding; Noreen J. Evans; Fang Xu; Wei-Ming Fan; Li-Yun Zhang; Fu-Long Cai; Qiu-Yun Guan; Ya-Hui Yue; Jing Xie (Lithos, 2024)

An intelligent dual stimuli-responsive Pickering emulsion for highly efficiently producing waste frying oil-based biodiesel - Jia-Liang Guo; Qing-Qing Sun; Zhong-Qiu Liu; Feng-Xiang Wang; Tingjun Fu; Yujing Liu; Anguo Ying (Journal of Cleaner Production, 2024)

Stability analysis of unsaturated soil slopes with cracks under rainfall infiltration conditions - Lei Zhang; Xin Jiang; Rong Sun; Hanyan Gu; Yongguo Fu; Yanjun Qiu (Computers and Geotechnics, 2024)

A metal-phenolic network-assembled nanotrigger evokes lethal ferroptosis via self-supply loop-based cytotoxic reactions - Xinping Zhang; Yuxin Guo; Xiaoyang Liu; Shun-Yu Wu; Ya-Xuan Zhu; Shao-Zhe Wang; Qiu-Yi Duan; Ke-Fei Xu; Zi-Heng Li; Xiao-Yu Zhu; Guang-Yu Pan; Fu-Gen Wu (Chemical Engineering Journal, 2024)

Assessing the impact of marketization on energy poverty - Xinjie Shi; Pei Zeng; Liu Cui; Xuwen Gao; Tongwei Qiu; Qiang Jiang; Linlin Fu (Environment, Development and Sustainability, 2023)

S-scheme MOF-on-MOF heterojunctions for enhanced photo-Fenton Cr(VI) reduction and antibacterial effects - Longyang Wang; Kejie Zhang; Jianying Qian; Mengyi Qiu; Ningyi Li; Hao Du; Xiao Hu; Yangjie Fu; Meng Tan; Derek Hao; Qi Wang (Chemosphere, 2023)

Tumor suppressive activity of AHR in environmental arsenic-induced carcinogenesis - Ziwei Wang; Yao Fu; Akimasa Seno; Zhuoyue Bi; Aashna S. Pawar; Haoyan Ji; Bandar Saeed Almutairy; Yiran Qiu; Wenxuan Zhang; Chitra Thakur; Fei Chen (Toxicology and Applied Pharmacology, 2023)

Adverse effects of plastic leachate and its component 2,4-DTBP on the early development of zebrafish embryos - Aifeng Li; Chen Yan; Jiangbing Qiu; Ying Ji; Yilei Fu; Wenhui Yan (Science of The Total Environment, 2023)

Experimental and kinetic study on the cyclic removal of low concentration CO2 by amine adsorbents in confined spaces - Pu Huang; Jiali Fu; Dongya Qiu; Zhengjun Gu; Jian Sun; Yafei Guo; Chuanwen Zhao (Process Safety and Environmental Protection, 2023)

How does social learning influence Chinese farmers’ safe pesticide use behavior? An analysis based on a moderated mediation effect - Dakuan Qiao; Lei Luo; Chaoyue Chen; Ling Qiu; Xinhong Fu (Journal of Cleaner Production, 2023)

Assessing the ecological risk of croplands in loess drylands by combining environmental disturbance with ecosystem vulnerability - Menglong Qiu; Mengyu Fu; Zhiwei Zhang; Shaowu Fu; Chengcheng Yuan (Journal of Environmental Management, 2023)

Achieving partial nitrification: A strategy for washing NOB out under high DO condition - Kunming Fu; Yihao Bian; Fan Yang; Jian Xu; Fuguo Qiu (Journal of Environmental Management, 2023)

One-pot high-speed shear preparation of modified straw: An efficient, convenient, nontoxic, and green method with high adsorption capacity for nitrate removal from aqueous solution - Lisheng Zhang; Weilin Fu; Shangkai Qiu; Mengmeng Li; Menghan Feng; Mingyao Yuan; Changbin Guo; Keqiang Zhang; Feng Wang; Wenjia Han (Journal of Environmental Chemical Engineering, 2023)

Improving the flavor of tilapia fish head soup by adding lipid oxidation products and cysteine - Huixian Fu; Qiaohui Feng; Dan Qiu; Xuanri Shen; Chuan Li; Yanfu He; Wenting Shang (Food Chemistry, 2023)

Self-standing metal-organic frameworks and their derivatives for electrochemical energy storage and conversion: Current progress and perspectives - Zhuozhao Wu; Jingwen Qiu; Gangwen Fu; Ruiyi Jiang; Danwei Zhang; Xi Xu (Chemical Engineering Journal, 2023)

Selenium-enriched Bacillus subtilis Improves Growth Performance, Antioxidant Capacity, Immune Status, and Gut Health of Broiler Chickens - Huiling Qiu; Shansong Gao; Lele Hou; Anping Li; Lian-qin Zhu; Jihong Dong; Fu Chen (Biological Trace Element Research, 2023)

Testing the factors on the evolution of movement-based visual signal complexity in an Asian agamid lizard - Yusong Lin; Xia Qiu; Jinzhong Fu; Richard Peters; Yin Qi (Behavioral Ecology and Sociobiology, 2023)

Research on cooperative's information services, farmers' cognition, and fertilizer reduction behavior: evidence from China - Xiaoyu Liu; Junlan Xiang; Ling Qiu; Xinhong Fu; Yuying Liu (Environment, Development and Sustainability, 2023)

Candidatus Accumulibacter use fermentation products for enhanced biological phosphorus removal - Liping Chen; Gengrui Wei; Yushen Zhang; Kaiying Wang; Cenchao Wang; Xuhan Deng; Yaqian Li; Xiaojing Xie; Jinling Chen; Fu Huang; Hang Chen; Bin Zhang; et al. (Water Research, 2023)

A novel culture-enriched metagenomic sequencing strategy effectively guarantee the microbial safety of drinking water by uncovering the low abundance pathogens - Songzhe Fu; Yixiang Zhang; Rui Wang; Zhiguang Qiu; Weizhi Song; Qian Yang; Lixin Shen (Journal of Environmental Management, 2023)

Association between prenatal exposure to per- and polyfluoroalkyl substances and neurodevelopment in children: Evidence based on birth cohort - Xin-xin Gao; Qian-lin Zuo; Xi-hang Fu; Ling-ling Song; Man-qiu Cen; Jing Wu (Environmental Research, 2023)

Analytical solutions for contaminant transport through a GMB/CCL composite liner system considering effective porosity and thermodiffusion - Jin-Wei Qiu; Lu-Sha Jiang; He-Fu Pu; Ding-Bao Song; Ming Min; Jun Tong (Computers and Geotechnics, 2023)

Livestock wastes from family-operated farms are potential important sources of potentially toxic elements, antibiotics, and estrogens in rural areas in North China - Yang Li; Xinyu Li; Xupu Ma; Tianlei Qiu; Xincheng Fu; Zhihong Ma; Hua Ping; Cheng Li (Environmental Science and Pollution Research, 2023)

Analysis and prediction of rockburst intensity using improved D-S evidence theory based on multiple machine learning algorithms - Daohong Qiu; Xuebing Li; Yiguo Xue; Kang Fu; Wenqing Zhang; Tao Shao; Yusong Fu (Tunnelling and Underground Space Technology, 2023)

The conversion of organic sulfur and strontium into inorganic compounds during the molten salt oxidation of mixed resin - Xin Liu; Yong-De Yan; Yang-Hai Zheng; Wen-Da Xu; Yun Xue; Jing-Ping Wang; Qing-Guo Zhang; Yue-Lin Wang; Fu-Qiu Ma (Journal of Environmental Chemical Engineering, 2023)

The youngest lunar zircon reveals an extremely fractionated nature of Chang’e-5 basalt - Qin Zhou; Yu Liu; Saihong Yang; Qiu-Li Li; Yi Chen; Guangliang Zhang; Hongbo Zhang; Bin Liu; Dawei Liu; Jianjun Liu; Fu-Yuan Wu; Xian-Hua Li; et al. (Geochimica et Cosmochimica Acta, 2023)

Spontaneous vertical phase distribution of multi-acceptors system enables high-efficiency organic photovoltaics in non-halogenated solvent and large-area module application - Xiangyue Kong; Lingling Zhan; Shuixing Li; Shouchun Yin; Huayu Qiu; Yuang Fu; Xinhui Lu; Zeng Chen; Haiming Zhu; Weifei Fu; Hongzheng Chen (Chemical Engineering Journal, 2023)

Kinetin inhibits hepatic stellate cell activation and induces apoptosis via interactions with the TGF-β1/Smad signaling pathway - Fu-chang Jin; Jing-jing Chen; Qiu-xian Xu; Ming-Hui Zhou; Yi Lin; Qi-wei Zhang; Chang-chun Zhang; Zhen-gang Zhang (Toxicology and Applied Pharmacology, 2023)

Soil development following glacier retreat shapes metagenomic and metabolomic functioning associated with asynchronous C and N accumulation - Yu Huang; Wei Shi; Qi Fu; Yingbo Qiu; Jiayi Zhao; Jiaxin Li; Qian Lyu; Xian Yang; Jia Xiong; Wenzhi Wang; Ruiying Chang; Zhiyuan Yao; et al. (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Phase-mediated mercury removal from water using multilayered molybdenum disulfide: The key role of redox mechanism - Jia Sun; Junjun Pei; Zhiyuan Qiu; Jing Guo; Bo Li; Kaixing Fu; Kai Yin; Shenglian Luo (Journal of Cleaner Production, 2023)

Local provincialism of late Permian plant–arthropod associations in South Cathaysia: Evidence of arthropod-mediated damages in a Wuchiapingian assemblage of South China - Fu-Jun Ma; Die-Die Luo; Song Liu; Cheng-Wan Zhang; Qiu-Jun Wang; Bing-Xia Li; Chuan-Yuan Liu; Bai-Nian Sun; Xiao He (Journal of Asian Earth Sciences, 2023)

Clinical poisoning events involving yunaconitine may be highly correlated with metabolism-based interactions: A critical role of CYP3A4 - Xiaocui Li; Yu Fu; Huawei Qiu; Xueyu Xu; Tingting Lin; Weiqing Hou; Weiying Chen; Rong Zhang; Zhongqiu Liu; Lijun Zhu (Food and Chemical Toxicology, 2023)

Revolutionizing wound healing: Ultrashort pulse electric fields in seconds for highly aligned extracellular matrix and efficient cell migration - Xiao-Wei Xiang; Hao-Tian Liu; Wei Liu; Ze-Yao Yan; Yu-Lian Zeng; Ya-Jun Wang; Jing Liu; Yu-Chen Chen; Sai-Xi Yu; Cai-Hui Zhu; Xiao-Nan Tao; Chen Wang; et al. (Chemical Engineering Journal, 2023)

A new oleanane-type triterpene from Ardisia lindleyana D.Dietr and its cytotoxic activity - Zhou Tiqiang; Wei Zhenzhen; Fu Qianyu; Qiu Rui; Zhang Guangjie; Li Bin; Dong Junxing; Zeng Chengchu (Natural Product Research, 2023)

Effect of copper ions on transformation of organic sulfur in cationic exchange resins in Li2CO3–Na2CO3–K2CO3 molten-salt system - Zhi Zhang; Yun Xue; Yue-Lin Wang; Wen-Da Xu; Yong-De Yan; Yang-Hai Zheng; Fu-Qiu Ma; Guo-Qiang Li (Chemosphere, 2023)

Dihydromyricetin attenuates cisplatin-induced acute kidney injury by reducing oxidative stress, inflammation and ferroptosis - Zheming Xu; Minjing Zhang; Wenwen Wang; Suhan Zhou; Minghua Yu; Xingyu Qiu; Shan Jiang; Xiaohua Wang; Chun Tang; Shuijie Li; Chih-Hong Wang; Runzhi Zhu; et al. (Toxicology and Applied Pharmacology, 2023)

Integrating decision-making preferences into ecosystem service conservation area identification: A case study of water-related ecosystem services in the Dawen River watershed, China - Kai Li; Ying Hou; Qi Fu; Mark Taylor Randall; Peter Stubkjær Andersen; Mingkun Qiu; Hans Skov-Petersen (Journal of Environmental Management, 2023)

A novel AD theranostic platform with NIR-II laser controlled drug release and real-time monitoring of therapeutic outcomes - Zhili Qiu; Guojun Cao; Shanrong Lv; Dehong Yu; Jingjing Fu; Hanrong Yan; Yuting Li; Peng Zhou; Xiunan Wu; Zhao Liu; Fenglei Gao (Chemical Engineering Journal, 2023)

Distinct resting-state functional connectivity patterns of Anterior Insula affected by smoking in mild cognitive impairment - Tianyi Zhang; Qingze Zeng; Kaicheng Li; Xiaocao Liu; Yanv Fu; Tiantian Qiu; Peiyu Huang; Xiao Luo; Zhirong Liu; Guoping Peng (Brain Imaging and Behavior, 2023)
Smoking is a modifiable risk factor for Alzheimer’s disease (AD). The insula plays a vital role in both smoking and cognition. However, the smoking effects on insula-related networks in cognitively normal controls (CN) and mild cognitive impairment (MCI) patients remain unknown. We identified 129 CN (85 non-smokers and 44 smokers) and 83 MCI (54 non-smokers and 29 smokers). Each underwent neuropsychological assessment and MRI (structural and resting-state functional). Seed-based functional analyses in the anterior and posterior insula were performed to calculate the functional connectivity (FC) with voxels in the whole brain. Mixed-effect analyses were performed to explore the interactive effects on smoking and cognitive status. Associations between FC and neuropsychological scales were assessed. Mixed-effect analyses revealed the FC differences between the right anterior insula (RAI) with the left middle temporal gyrus (LMTG) and that with the right inferior parietal lobule (RIPL) ( p < 0.01, cluster level < 0.05, two-tailed, gaussian random field correction). The FC of RAI in both LMTG and RIPL sees a significant decrease in MCI smokers ( p < 0.01). Smoking affects insula FC differently between MCI and CN, and could decrease the insula FC in MCI patients. Our study provides evidence of neural mechanisms between smoking and AD.

Self-Interference Suppression of Unmanned Underwater Vehicle with Vector Hydrophone Array Based on an Improved Autoencoder - Jin Fu; Wenfeng Dong; Longhao Qiu; Chunpeng Zhao; Zherui Wang (Journal of Marine Science and Engineering, 2023)
The self-interference of an unmanned underwater vehicle (UUV) weakens its ability to detect targets of interest. Due to limitations in the size of the sonar array and the complexity of the interference, the performance of existing self-interference suppression methods in practical applications is unsatisfactory. Our research focuses on analyzing the influence of near-field interferences on the sample covariance matrix (SCM) and proposes an interference suppression algorithm based on an improved autoencoder. The proposed algorithm effectively learns the feature distribution of near-field interferences within the covariance domain and reconstructs the pure signal covariance matrix through the cancellation of the near-field interference features. Moreover, the proposed algorithm can meet the requirements of real-time processing and does not require prior knowledge about the positions or propagation of interference. Simulations demonstrate that the proposed algorithm outperforms comparison methods, particularly in scenarios with low signal-to-interference ratios and a limited number of sensors. Furthermore, lake experiments provide additional evidence of the proposed algorithm’s good performance in practical applications.

Essential oil diversity of Cinnamomum parthenoxylon (Jack) Meisner from China - Fengying Qiu; Haikuan Yang; Chao Fu; Songsong Zhou; Yajing Sheng; Ting Zhang (South African Journal of Botany, 2023)

Polyacrylonitrile fiber with light-driven intelligent reversible and switchable wettability as an environmental benign solid base for biodiesel production - Huan-Xing Zhou; Qing-Qing Sun; Zhong-Qiu Liu; Jie-Wen Duan; Tingjun Fu; Yujing Liu; Anguo Ying (Journal of Cleaner Production, 2023)

Fully coupled two-phase hydro-mechanical model for wellbore stability analysis in tight gas formations considering the variation of rock mechanical parameters - Jinhua Liu; Tianshou Ma; Jianhong Fu; Nian Peng; Yi Qiu; Yang Liu; Jiajia Gao (Gas Science and Engineering, 2023)

Pomelo peel derived nanocellulose as Pickering stabilizers: Fabrication of Pickering emulsions and their potential as sustained-release delivery systems for lycopene - Jianbiao Gao; Yihua Qiu; Fu Chen; Lujia Zhang; Wei Wei; Xingye An; Qiaomei Zhu (Food Chemistry, 2023)

Regulation of innate immunity in marine mussel Mytilus coruscus: MicroRNA Mc-novel_miR_196 targets McTLR-like1 molecule to inhibit inflammatory response and apoptosis - Yashu Wu; Xirui Si; Longmei Qiu; Xinglu Chen; Peipei Fu; Isabella Buttino; Baoying Guo; Zhi Liao; Xiaojun Yan; Pengzhi Qi (Fish & Shellfish Immunology, 2023)

Can the mix-charged NF membrane directly obtained by the interfacial polymerization of PIP and TMC? - Qiu-Yu Zhu; Zi-Yun Xu; Jie-Han Fu; Jie Huang; Zhen-Liang Xu; Min Tong; En-Chao Li; Yong-Jian Tang (Desalination, 2023)

Near unity broadband emissivity and ultralow thermal conductivity from yttrium niobate-based ceramics - Guoliang Chen; Benzhi Min; Haoyang Fu; Siqi Ma; Ke Li; Shuqi Wang; Yaming Wang; Jianyun Cao; Jun Qiu; Yong Shuai; Shuzhou Li; Yongchun Zou; et al. (Chemical Engineering Journal, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Ca–La layered double hydroxide (LDH) for selective and efficient removal of phosphate from wastewater - Yuhang Cao; Xuewei Wu; Biqing Li; Xia Tang; Xueran Lin; Pengfei Li; Hang Chen; Fu Huang; Chaohai Wei; Jian Wei; Guanglei Qiu (Chemosphere, 2023)

Colletotrins A-C, three new sesquiterpenes from the endophytic fungus Colletotrichum iris strain S11 - Ning Chen; Shi-Yu Qiu; Song-Mei Lu; Shi-Wei Chen; Ji-Rui Wei; Fu-Wen Yang; Hui-Chun Geng; Min Zhou (Phytochemistry Letters, 2023)

Pheromone effect of estradiol regulates the conjugative transfer of pCF10 carrying antibiotic resistance genes - Xiaobo Yang; Yuanyuan Niu; Yutong Yang; Hongrui Zhou; Jing Li; Xinyue Fu; Zhiqiang Shen; Jingfeng Wang; Zhigang Qiu (Journal of Hazardous Materials, 2023)

Simultaneous and long-term effective immobilization of lead, cadmium and arsenic in multi-contaminated soil by ferrihydrite-supported animal-derived biochar - Chengyi Hong; Jichen Zhang; Tingran Liu; Wei Teng; Rongbing Fu; Yuping Qiu (Journal of Environmental Chemical Engineering, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

Cell cycle of microalga Isochrysis galbana arrested by neurotoxin β-N-methylamino-l-alanine and corresponding molecular mechanisms - Aifeng Li; Jianwei Liu; Jiangbing Qiu; Guixiang Wang; Xianyao Zheng; Ying Ji; Guowang Yan; Peng Zhao; Xizhen Wu; Wenhui Yan; Lei Zhang; Min Li; et al. (Science of The Total Environment, 2023)

B-site metal modulation of phosphate adsorption properties and mechanism of LaBO3 (B = Fe, Al and Mn) perovskites - Changbin Guo; Mengmeng Li; Menghan Feng; Mingyao Yuan; Shangkai Qiu; Lisheng Zhang; Weilin Fu; Jien Zhou; Keqiang Zhang; Yanli Luo; Feng Wang (Environmental Science and Pollution Research, 2023)

Identifying the water quality variation characteristics and their main driving factors from 2008 to 2020 in the Yellow River Basin, China - Shasha Liu; Yue Qiu; Rui Fu; Yun Liu; Chengyu Suo (Environmental Science and Pollution Research, 2023)

Vitamin C down-regulates the H3K9me3-dependent heterochromatin in buffalo fibroblasts via PI3K/PDK1/SGK1/KDM4A signal axis - Jinling Wang; Lei Wang; Zhiqiang Wang; Meiyun Lv; Jiayuan Fu; Yunchuan Zhang; Peng Qiu; Deshun Shi; Chan Luo (Theriogenology, 2023)

Probabilistic determination and application of rock thickness resisting water inrush from karst cave - Zhi-Qiang Li; Yiguo Xue; Guangkun Li; Daohong Qiu; Lei Xu; Qiushi Liu; Kang Fu (Process Safety and Environmental Protection, 2023)

Exosomes Derived from Human Amniotic Mesenchymal Stem Cells Facilitate Diabetic Wound Healing by Angiogenesis and Enrich Multiple lncRNAs - Shangfeng Fu; Hongyan Zhang; Xiancai Li; Qiling Zhang; Chunyan Guo; Keqing Qiu; Junyun Feng; Xiaoxiao Liu; Dewu Liu (Tissue Engineering and Regenerative Medicine, 2023)

Photoinduced transformation of ferrihydrite in the presence of aqueous sulfite and its influence on the repartitioning of Cd - Jinwen Qiu; Xiaokang Hou; Yuan Ren; Chengshuai Liu; Fangyuan Meng; Jyh-Fu Lee; Yu-Jung Lin; Ziyuan Huang; Huanxin Ma; Zhenqing Shi; Chunhua Feng (Water Research, 2023)

Biodegradation of phthalate isomers by newly isolated Klebsiella variico SY1 and its functional genomic analysis - Lequan Qiu; Chenyu Li; Yanan Fu; Ying Wang; Zijie Zhang; Zhi Zuo; Ruifeng Chen; Xinge Yin; Tongtong Li; Shijin Wu (International Biodeterioration & Biodegradation, 2023)

No tillage outperforms conventional tillage under arid conditions and following fertilization - Stavros D. Veresoglou; Junjiang Chen; Xuheng Du; Qi Fu; QingLiu Geng; Chenyan Huang; Xilin Huang; Nan Hu; Yiming Hun; Guolin C. Li; Zhiman Lin; Zhiyu Ma; et al. (Soil Ecology Letters, 2023)

The MocR family transcriptional regulator DnfR has multiple binding sites and regulates Dirammox gene transcription in Alcaligenes faecalis JQ135 - Si‐Qiong Xu; Xiao Wang; Lu Xu; Ke‐Xin Wang; Yin‐Hu Jiang; Fu‐Yin Zhang; Qing Hong; Jian He; Shuang‐Jiang Liu; Ji‐Guo Qiu (Environmental Microbiology, 2023)
Microbial ammonia oxidation is vital to the nitrogen cycle. A biological process, called Dirammox ( dir ect amm onia ox idation, NH 3 →NH 2 OH→N 2 ), has been recently identified in Alcaligenes ammonioxydans and Alcaligenes faecalis . However, its transcriptional regulatory mechanism has not yet been fully elucidated. The present study characterized a new MocR‐like transcription factor DnfR that is involved in the Dirammox process in A. faecalis strain JQ135. The entire dnf cluster was composed of 10 genes and transcribed as five transcriptional units, that is, dnfIH , dnfR , dnfG , dnfABCDE and dnfF . DnfR activates the transcription of dnfIH , dnfG and dnfABCDE genes, and represses its own transcription. The intact 1506‐bp dnfR gene was required for activation of Dirammox. Electrophoretic mobility shift assays and DNase I footprinting analyses showed that DnfR has one binding site in the dnfH ‐ dnfR intergenic region and two binding sites in the dnfG ‐ dnfA intergenic region. Three binding sites of DnfR shared a 6‐bp repeated conserved sequence 5′‐GGTCTG‐N 17 ‐GGTCTG‐3′ which was essential for the transcription of downstream target genes. Cysteine and glutamate act as possible effectors of DnfR to activate the transcription of transcriptional units of dnfG and dnfABCDE , respectively. This study provided new insights in the transcriptional regulation mechanism of Dirammox by DnfR in A. faecalis JQ135.

Investigation and optimization of methane purification method for natural gas by two-column gas chromatography: A preliminary test for doubly substituted isotopologue (13CH3D) measurements - Tiantian Sun; Jun Cao; Haijun Qiu; Piaoer Fu; Hailong Lu; Zijie Ning; Daohua Chen; Yinan Deng; Shengxiong Yang (Frontiers in Marine Science, 2023)
In this study, optimization of the methane purification method by gas chromatography (GC) is described for the determination of methane clumped isotope compositions of natural gas. Methane was purified under the carrying of helium on the assembly line composed of a vacuum apparatus and two-column gas chromatography. Once methane was detected by the passive thermal conductivity detector (TCD) on the GC, it was collected through a silica trap immersed in liquid nitrogen. Optimum conditions of chromatographic column diameter (1/4 inch outside diameter), temperature (25 °C), and flow rate (50.8 ml min -1 ) have been determined. When N 2 /CH 4 (by volume) is<8.7%, the purification experiment can be undertaken once, while a double purification experiment is required when natural gas samples have an N 2 /CH 4 of 8.7-78.0%. The purification method yielded a purity of 98.4-98.8% with a recovery of 97.3-98.7% on purified methane samples verified by GC determination. N 2 was the main source that contributed to the loss of the purity, however, the N-bearing isobaric interferences ( 14 NH 3 + and 14 NH 4 + ) in purified samples presented<1‰ intensity compared to the methane isotopologues ( 13 CH 4 + and 13 CH 3 D + ), thus we concluded that these interferences have no impact on clumped isotope determinations. The conventional δ 13 C VPDB and δD VSMOW values of purified methane samples were consistent with those of pure methane. A preliminary measurement of Δ 13 CH 3 D (working gas) of purified samples revealed differences of -0.27‰, which was within the internal precision of the measurement. The entire process of a single purification can be completed within two hours. Our proposed method could be used for the clumped isotope purification of natural gas with higher than ~50% methane.

Docosahexaenoic acid inhibits pheromone-responsive-plasmid-mediated conjugative transfer of antibiotic resistance genes in Enterococcus faecalis - Hongrui Zhou; Xiaobo Yang; Yutong Yang; Yuanyuan Niu; Jing Li; Xinyue Fu; Shang Wang; Bin Xue; Chenyu Li; Chen Zhao; Xi Zhang; Zhiqiang Shen; et al. (Journal of Hazardous Materials, 2023)

Effect of phenol formaldehyde-associated microplastics on soil microbial community, assembly, and functioning - Hu Li; Qiu-Ping Luo; Sha Zhao; Yan-Yan Zhou; Fu-Yi Huang; Xiao-Ru Yang; Jian-Qiang Su (Journal of Hazardous Materials, 2023)

Enhancing phosphate removal performance in water using La–Ca/Fe–LDH: La loading alleviates ineffective stacking of laminates and increases the number of active adsorption sites - Mingyao Yuan; Shangkai Qiu; Mengmeng Li; Zhao Di; Menghan Feng; Changbin Guo; Weilin Fu; Keqiang Zhang; Wenxian Hu; Feng Wang (Journal of Cleaner Production, 2023)

Analytical solution for coupled water–gas transport in unsaturated landfill cover system with different root architectures - Ming Min; He-Fu Pu; Song Feng; Jin-Wei Qiu; Xiao-Jun Wen (Computers and Geotechnics, 2023)

Tailored chemically bonded metal phosphide@carbon nanowire arrays on foam metal as an all-in-one anode for ultrahigh-area-capacity sodium-ion batteries - Yuyan Qiu; Fang Fu; Miao Hu; Pei Kang Shen; Jinliang Zhu (Chemical Engineering Journal, 2023)

AIFM1 variants associated with auditory neuropathy spectrum disorder cause apoptosis due to impaired apoptosis-inducing factor dimerization - Yue Qiu; Hongyang Wang; Huaye Pan; Jing Guan; Lei Yan; Mingjie Fan; Hui Zhou; Xuanhao Zhou; Kaiwen Wu; Zexiao Jia; Qianqian Zhuang; Zhaoying Lei; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

Alleviation of aqueous nitrogen loss from paddy fields by growth and decomposition of duckweed (Lemna minor L.) after fertilization - Yuan Wang; Xiaodong Chen; Bin Guo; Chen Liu; Junli Liu; Gaoyang Qiu; Qinglin Fu; Hua Li (Chemosphere, 2023)

Detection and attribution of urbanization impact on summer extreme heat based on nonstationary models in the Yangtze River Delta, China - Pengcheng Xu; Yuankun Wang; Xiaolei Fu; Vijay P. Singh; Jianchun Qiu (Urban Climate, 2023)

Development of quantitative wastewater surveillance models facilitated the precise epidemic management of COVID-19 - Songzhe Fu; Fenglan He; Rui Wang; Wentao Song; Qingyao Wang; Wen Xia; Zhiguang Qiu (Science of The Total Environment, 2023)

The growth-regulating factor PdbGRF1 positively regulates the salt stress response in Populus davidiana × P. bolleana - Zhong-Yuan Liu; Ya-Ting Han; Chun-Yao Wang; Xiao-Jin Lei; Yuan-Yuan Wang; Wen-Fang Dong; Qing-Jun Xie; Yu-Jie Fu; Cai-Qiu Gao (Plant Science, 2023)

Examining the relationship between built environment and urban parking demand from the perspective of travelers - Tao Peng; Jian Chen; Keliang Liu; Zhixuan Qiu; Zhiyan Fu; Yong Huang (Journal of Cleaner Production, 2023)

Thermodynamic characteristics of methane hydrate formation in high-pressure microcalorimeter under different reaction kinetics - Juan Fu; Jia-Mei Mo; Shi-Jun Liu; Wen-Zhe Yi; Yi-Song Yu; Neng-You Wu; Xiao-Li Chen; Qiu-Cheng Su; Xiao-Sen Li (Fuel, 2023)

Performance and mechanisms for tetrabromobisphenol A efficient degradation in a novel homogeneous advanced treatment based on S2O42− activated by Fe3+ - Wei Song; Mu Li; Sen Xu; Zhuoyue Wang; Ji Li; Xiaolei Zhang; Wenhui Qiu; Zhihong Wang; Qi Song; Kalpana Bhatt; Caixia Fu (Environmental Pollution, 2023)

Efficient enrichment of iodine by supported ionic liquid with three effective adsorption sites: Heteroatoms, fused aromatic rings and ionic bond - Yu-Qin Xiang; Yuan-Hao Wang; Hao Chen; Jie Fu; Qiu-Hong Zhu; Xiao-Lan Yang; Xin-Hong Xu; Song Qin; Ling He; Guo-Hong Tao (Chemical Engineering Journal, 2023)

Superhydrophobic cellulosic triboelectric materials for distributed energy harvesting - Chenyuan Zhang; Wanglin Zhang; Guoli Du; Qiu Fu; Jilong Mo; Shuangxi Nie (Chemical Engineering Journal, 2023)

Enhanced cellulosic d-lactic acid production from sugarcane bagasse by pre-fermentation of water-soluble carbohydrates before acid pretreatment - Zhongyang Qiu; Xushen Han; Anqing Fu; Yalan Jiang; Wenyue Zhang; Ci Jin; Dengchao Li; Jun Xia; Jianlong He; Yuanfang Deng; Ning Xu; Xiaoyan Liu; et al. (Bioresource Technology, 2023)

Gut microbiota involved in spermatogenic function of Sancai Lianmei granules in obese mice - Yuguo Xia; Ying Tian; Dongqi Zhou; Lei Zhang; Yichen Cai; Shunlian Fu; Xiaoran Zhang; Yang Gao; Qiu Chen; Ping Gao (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Association between pyrethroid exposure and risk of depressive symptoms in the general US adults - Hui-ru Li; Xi-hang Fu; Ling-ling Song; Man-qiu Cen; Jing Wu (Environmental Science and Pollution Research, 2023)

Zinc supplementation ameliorates sorafenib-induced cognitive impairment through ROS/JNK signaling pathway - Can-Can Zhou; Yu-Qiong He; Yu-Shuang Qiu; Chen-Xu Ni; Fu-Ming Shen; Dong-Jie Li (Biological Trace Element Research, 2023)

Influence of flooding on GPS carrier-to-noise ratio and water content variation analysis: a case study in Zhengzhou, China - Mingkun Su; Fu Zheng; Junna Shang; Lei Qiao; Zhaoyang Qiu; Huan Zhang; Jiansheng Zheng (GPS Solutions, 2023)

Effects of the neurotoxin β-N-methylamino-L-alanine (BMAA) on the early embryonic development of marine shellfish and fish - Yilei Fu; Aifeng Li; Jiangbing Qiu; Wenhui Yan; Chen Yan; Lei Zhang; Min Li (Frontiers in Marine Science, 2022)
The neurotoxin β - N -methylamino- L -alanine (BMAA) produced by cyanobacteria and diatoms can accumulate in diverse aquatic organisms through the food web. In the present study, embryos of mussel Mytilus galloprovincialis (Lamarck, 1819), oyster Magallana gigas (Thunberg, 1793), and marine medaka Oryzias melastigma (McClelland, 1839) were exposed to BMAA dissolved in seawater and monitored for early developmental effects. Results demonstrated that the embryonic development of mussels and oysters were significantly inhibited when BMAA concentrations were above 100 μg BMAA·HCl/L (0.65 µM) and 800 μg BMAA·HCl/L (5.18 µM), respectively. The shell growth of mussel embryos was also markedly inhibited by BMAA ≥ 100 μg BMAA·HCl/L (0.65 µM). Based on the dose-response curves related to the modified malformation rate of embryos, the median effective concentration (EC 50 ) values of mussel (48 h) and oyster (24 h) embryos were 196 μg BMAA·HCl/L (1.27 µM) and 1660 μg BMAA·HCl/L (10.7 μM), respectively. A sustained and dose-dependent decrease in heart rate was apparent in marine medaka embryos at 9-days post fertilization following BMAA exposure. However, no obvious effect on ATP concentration was noted in these marine medaka embryos. The current study contributes to our understanding of the sublethal effects of BMAA on the early embryonic development of marine bivalves and medaka. Further research examining the long-term effects of BMAA on the early development of marine organisms is necessary to determine seawater quality criteria for protection.

Effects of oxygen content on gaseous and solid products during molten salt oxidation of cation exchange resins - Yun Xue; Yue-Lin Wang; Yang-Hai Zheng; Yu-Sheng Yang; Wen-Da Xu; Yong-De Yan; Ran Zhao; Qing-Guo Zhang; Xin Liu; Fu-Qiu Ma; Mi-Lin Zhang (Environmental Science and Pollution Research, 2022)

Inhibition of Microglial NLRP3 with MCC950 Attenuates Microglial Morphology and NLRP3/Caspase-1/IL-1β Signaling In Stress-induced Mice - Qing Liu; Man-Man Zhang; Min-Xia Guo; Qiu-Ping Zhang; Na-Zhi Li; Jie Cheng; Shi-Le Wang; Guang-Hui Xu; Cheng-Fu Li; Ji-Xiao Zhu; Li-Tao Yi (Journal of Neuroimmune Pharmacology, 2022)

BCI system with lower-limb robot improves rehabilitation in spinal cord injury patients through short-term training: a pilot study - Zhengzhe Cui; Yongqiang Li; Sisi Huang; Xixi Wu; Xiangxiang Fu; Fei Liu; Xiaojiao Wan; Xue Wang; Yuting Zhang; Huaide Qiu; Fang Chen; Peijin Yang; et al. (Cognitive Neurodynamics, 2022)

Evolution mechanism and deformation stability analysis of rock slope block toppling for early warnings - Jian-qiao Mu; Tian-tao Li; Xiang-jun Pei; Run-qiu Huang; Fu-an Lan; Xue-qing Zou (Natural Hazards, 2022)

ATF3 in atherosclerosis: a controversial transcription factor - Bingyu Wang; Xi Yang; Xinyi Sun; Jianhui Liu; Yin Fu; Bingyang Liu; Jun Qiu; Jiangfang Lian; Jianqing Zhou (Journal of Molecular Medicine, 2022)

Monoterpenoid indole alkaloids with potential neuroprotective activities from the stems and leaves of Melodinus cochinchinensis - Yu-Jie Li; Juan Li; Lan Xie; Jun-Yu Zhou; Qiu-Xuan Li; Rui-Yuan Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2022)

Investigation of migration rule of rainwater for sponge city roads under different rainfall intensities - Zhe Qin; Yujing Yao; Jingwei Zhao; Houli Fu; Sheng Zhang; Liyuan Qiu (Environmental Geochemistry and Health, 2022)

Catalytic effect of cesium on the oxidation behavior of cation exchange resins in Li2CO3-Na2CO3-K2CO3 melt - Yang-Hai Zheng; Yong-De Yan; Yun Xue; Yue-Lin Wang; Xin Liu; Wan-Sheng Mi; Qing-Guo Zhang; Yu Li; Fu-Qiu Ma; Mi-Lin Zhang; Zhi-Hao Gan; Kai Zhu (Environmental Science and Pollution Research, 2022)

Photocatalysis of aqueous PFOA by common catalysts of In2O3, Ga2O3, TiO2, CeO2 and CdS: influence factors and mechanistic insights - Caixia Fu; Xiuru Xu; Chunmiao Zheng; Xinjie Liu; Dandan Zhao; Wenhui Qiu (Environmental Geochemistry and Health, 2022)

Visualization experiments and seepage characteristics of water–solid mixture flow through a rough fracture of silty mudstone under low hydraulic head - Huangbin Jiang; Hongyuan Fu; Xiang Qiu; Jiangying Wang (Arabian Journal of Geosciences, 2022)

Ginsenoside Rb3 attenuates skin flap ischemia-reperfusion damage by inhibiting STING-IRF3 signaling - Yuanbin Li; Haifen Liu; Zhaohui Zeng; Hui Lin; Xin Chen; Xianglian Yuan; Jizhe Qiu; Fengchun Fu; Zhuang Chen; Jianjun Kuang (Journal of Molecular Histology, 2022)

Selenide Chitosan Sulfate Improved the Hepatocyte Activity, Growth Performance, and Anti-oxidation Capacity by Activating the Thioredoxin Reductase of Chickens In Vitro and In Vivo - Lele Hou; Huiling Qiu; Lianqin Zhu; Shansong Gao; Fu Chen (Biological Trace Element Research, 2022)

Rs7853346 Polymorphism in lncRNA-PTENP1 and rs1799864 Polymorphism in CCR2 are Associated with Radiotherapy-Induced Cognitive Impairment in Subjects with Glioma Via Regulating PTENP1/miR-19b/CCR2 Signaling Pathway - Sen Yang; Zhan-zhao Fu; Yan-qiu Zhang; Bao-hong Fu; Li-xin Dong (Biochemical Genetics, 2022)

Characteristics of summer cloud precipitation along latitude 30°N in East Asia derived from Tropical Rainfall Measuring Mission Precipitation Radar and Visible and Infrared Scanner measurements - Mengxiao Wang; Yunfei Fu; Chun Zhao; Lei Zhong; Rui Li; Dongyong Wang; Xuexing Qiu; Shengnan Zhou (International Journal of Climatology, 2022)
There has been little systematic analysis of the influence of the three‐step staircase topography on the characteristics of precipitation along latitude 30°N in East Asia. After the distribution of atmospheric climate states over East Asia was analysed, in this study, the climatological characteristics of summer convective and stratiform precipitation on horizontal distribution, vertical structure, and diurnal variation in East Asia were investigated by using a merged dataset derived from the measurements of the Tropical Rainfall Measuring Mission Precipitation Radar and Visible and Infrared Scanner from 1998 to 2012 reanalysis datasets. Results indicate that the rain frequency, the mean rain rate, and the maximum echo reflectivity factor show clear differences among the three‐step staircase topography, especially between the first staircase and its eastern region. There are small changes in the echo‐top height, the cloud‐top height, the maximum echo reflectivity factor and its corresponding height from the East China Sea westwards to the eastern part of the first staircase, passing the third staircase and the second staircase along 30°N. However, the rain rate decreased obviously twice westwards along this latitude, which responds to aerosol indirect effect and humidity effect, respectively. The diurnal variation of the convective precipitation reflectivity factor indicated that the development of convection in the eastern part of the first staircase gets at the maximum from the early afternoon to sunset, whereas the strongest echo reflectivity factor of precipitation in the second and third staircases including the East China Sea appears in the early morning, which is consistent with the diurnal variations of the atmospheric circulation.

CircLPAR3 Acts as an Oncogene in Oral Squamous Cell Carcinoma Through Regulating the miR-643/HMGB2 Network - Yunxia Fu; Chunyan Qiu; Yanjun Yang; Jianying Lu; Yun Qi (Biochemical Genetics, 2022)

Theoretical model and its experimental verification on nonlinear flow through a rough fracture of silty mudstone under low water head - Hongyuan Fu; Huangbin Jiang; Xiang Qiu; Ling Zeng; Qian-Feng Gao (Bulletin of Engineering Geology and the Environment, 2022)

Genome-wide identification of HD-ZIP transcription factors in maize and their regulatory roles in promoting drought tolerance - Xiao Qiu; GuoRui Wang; Salah Fatouh Abou-Elwafa; Jiaxu Fu; Zhixue Liu; PengYu Zhang; Xiaowen Xie; Lixia Ku; Ying Ma; XiaoKang Guan; Li Wei (Physiology and Molecular Biology of Plants, 2022)

Genetic diversity and structure of Oncomelania hupensis hupensis in two eco-epidemiological settings as revealed by the mitochondrial COX1 gene sequences - Jie-Ying Zhang; Man-Man Gu; Qiu-Fu Yu; Meng-Tao Sun; Hui-Ying Zou; Zhi-Jun Zhou; Da-Bing Lu (Molecular Biology Reports, 2022)

Response of the nuclear xenobiotic receptors to alleviate glyphosate-based herbicide-induced nephrotoxicity in weaned piglets - Shengnan Qiu; Yang Liu; Yanan Gao; Huiyang Fu; Baoming Shi (Environmental Science and Pollution Research, 2022)

Development characteristics of organic-inorganic pores in the mixed laminated shale of the saline fault lake basin - Qiang Fu; Zongquan Hu; Xuming Qiu; Shijie Zhao; Ji Teng; Hongliang Duan; Tingting Qin; Bing Yang (Arabian Journal of Geosciences, 2022)

Two new troponoides with anti-inflammatory activity from the stems of Juniperus formosana Hayata - Dong Zheng; Jian-Yu Zhang; Wen-Hao Fu; Shun-Zhi Liu; Su-Zhi Xie; Zheng Wang; Ying-Kun Qiu (Natural Product Research, 2021)

Erratum to: Settlement patterns of mountainous half-filled and half-cut widened subgrade with retaining wall - Yong-guo Fu; Xin Jiang; Han-yan Gu; Yan-jun Qiu (Journal of Mountain Science, 2021)

A novel regQTL-SNP and the risk of lung cancer: a multi-dimensional study - Yuhui Yu; Liping Mao; Zhounan Cheng; Xiaoqi Zhu; Jiahua Cui; Xiaoyu Fu; Jingwen Cheng; Yan Zhou; Anni Qiu; Yang Dong; Xun Zhuang; Yihua Lu; et al. (Archives of Toxicology, 2021)

Correction to: Considerations for Updates to ICH Q1 and Q5C Stability Guidelines: Embracing Current Technology and Risk Assessment Strategies - Megan E. McMahon; Alexander Abbott; Yelizaveta Babayan; Jenny Carhart; Chi-wan Chen; Elke Debie; Mingkun Fu; Cherokee Hoaglund-Hyzer; Andrew Lennard; Hanlin Li; Tony Mazzeo; Lori McCaig; et al. (The AAPS Journal, 2021)

Considerations for Updates to ICH Q1 and Q5C Stability Guidelines: Embracing Current Technology and Risk Assessment Strategies - Megan E. McMahon; Alexander Abbott; Yelizaveta Babayan; Jenny Carhart; Chi-wan Chen; Elke Debie; Mingkun Fu; Cherokee Hoaglund-Hyzer; Andrew Lennard; Hanlin Li; Tony Mazzeo; Lori McCaig; et al. (The AAPS Journal, 2021)

Transcriptome analysis reveals differing response and tolerance mechanism of EPSPS and GAT genes among transgenic soybeans - Bing-Fu Guo; Hui-Long Hong; Li-Ping Sun; Yong Guo; Li-Juan Qiu (Molecular Biology Reports, 2021)

Differential metabolism-associated gene expression of duck pancreatic cells in response to two strains of duck hepatitis A virus type 1 - Zhen Chen; Shao-hua Shi; Yu Huang; Cui-qin Huang; Rong-chang Liu; Long-fei Cheng; Guang-hua Fu; Hong-mei Chen; Chun-he Wan; Qiu-ling Fu (Archives of Virology, 2021)
Several outbreaks of duck hepatitis A virus type 1 (DHAV-1), which were characterized by yellow coloration and hemorrhage in pancreatic tissues, have occurred in China. The causative agent is called pancreatitis-associated DHAV-1. The mechanisms involved in pancreatitis-associated DHAV-1 infection are still unclear. Transcriptome analysis of duck pancreas infected with classical-type DHAV-1 and pancreatitis-associated DHAV-1 was carried out. Deep sequencing with Illumina-Solexa resulted in a total of 53.9 Gb of clean data from the cDNA library of the pancreas, and a total of 29,597 unigenes with an average length of 993.43 bp were generated by de novo sequence assembly. The expression levels of D-3-phosphoglycerate dehydrogenase, phosphoserine aminotransferase, and phosphoserine phosphatase, which are involved in glycine, serine, and threonine metabolism pathways, were significantly downregulated in ducks infected with pancreatitis-associated DHAV-1 compared with those infected with classical-type DHAV-1. These findings provide information regarding differences in expression levels of metabolism-associated genes between ducks infected with pancreatitis-associated DHAV-1 and those infected with classical-type DHAV-1, indicating that intensive metabolism disorders may contribute to the different phenotypes of DHAV-1-infection.

New types of ATP ‐grasp ligase are associated with the novel pathway for complicated mycosporine‐like amino acid production in desiccation‐tolerant cyanobacteria - Zhong‐Chun Zhang; Kai Wang; Fu‐Hua Hao; Jin‐Long Shang; Hui‐Ru Tang; Bao‐Sheng Qiu (Environmental Microbiology, 2021)
Summary Mycosporine‐like amino acids (MAAs) were widespread in diverse organisms to attenuate UV radiation. We recently characterized the large, complicated MAA mycosporine‐2‐(4‐deoxygadusolyl‐ornithine) in desert cyanobacterium Nostoc flagelliforme . Synthesis of this MAA requires the five‐gene cluster mysABDC2C3 . Here, bioinformatic analysis indicated that mysC duplication within five‐gene mys clusters is strictly limited to drought‐tolerant cyanobacteria. Phylogenic analysis distinguished these duplicated MysCs into two clades that separated from canonical MysCs. Heterologous expression of N. flagelliforme mys genes in Escherichia coli showed that MysAB produces 4‐deoxygadusol. The ATP‐grasp ligase of MysC3 catalyses the linkage of the δ‐ or ε‐amino group of ornithine/lysine to 4‐deoxygadusol, yielding mycosporine‐ornithine or mycosporine‐lysine respectively. The ATP‐grasp ligase of MysC2 strictly condenses the α‐amino group of mycosporine‐ornithine to another 4‐deoxygadusol. MysD (D‐Ala–D‐Ala ligase) functions following MysC2 to catalyse the formation of mycosporine‐2‐(4‐deoxygadusolyl‐ornithine). High arginine content likely provides a greater pool of ornithine over other amino acids during rehydration of desiccated N. flagelliforme . Duplication of ATP‐grasp ligases is specific for the use of substrates that have two amino groups (such as ornithine) for the production of complicated MAAs with multiple chromophores. This five‐enzyme biosynthesis pathway for complicated MAAs is a novel adaptation of cyanobacteria for UV tolerance in drought environments.

Settlement patterns of mountainous half-filled and half-cut widened subgrade with retaining wall - Yong-guo Fu; Xin Jiang; Han-yan Gu; Yan-jun Qiu (Journal of Mountain Science, 2021)

HDAC inhibitors improve CRISPR-mediated HDR editing efficiency in iPSCs - Jian-Ping Zhang; Zhi-Xue Yang; Feng Zhang; Ya-Wen Fu; Xin-Yue Dai; Wei Wen; Beldon Zhang; Hannah Choi; Wanqiu Chen; Meredith Brown; David Baylink; Lei Zhang; et al. (Science China Life Sciences, 2021)

Lean Stability Case Studies—Leveraging Science- and Risk-Based Approaches to Enable Meaningful Phase Specific Pharmaceutical Stability Strategies - Eric Adamec; Yelizaveta Babayan; Bruno Catacchio; Angela Coon; Allison Dill; Mingkun Fu; Lars Gruenig; Cherokee Hoaglund Hyzer; Michael Lesslie; Megan McMahon; Donnie Pulliam; Fenghe Qiu; et al. (Journal of Pharmaceutical Innovation, 2021)
Purpose Lean stability is a science- and risk-based initiative which utilizes the enhanced understanding of drug substance and drug product physical and chemical characteristics to (1) reduce and optimize the design of standard stability protocols; (2) expedite the generation of stability data without impact to safety, efficacy, or quality of the product; and (3) decrease time to market for innovative drugs. Lean stability was introduced in the early 2000s [ICH: Guideline Q1A(R2) (2003), ICH: Guideline Q1D (2002)] followed by reduced stability protocols, focusing on the critical quality attributes and critical time points, being reported in the literature [Skrdla et al. (J Pharm Biomed Anal 50: 794–796, 2009)]. While the concept of lean testing is not entirely new, and it is currently a part of several regulatory guidances, it continues to evolve and gain acceptance of the industry and regulators. Methods In this review, twelve case studies are presented where stability data was collected during clinical, registration, and post-approval phases of the product development. Results Case studies summarize the lean stability testing design, the strategies applied during the regulatory filing and the outcomes of the regulatory filings. Conclusion The authors expect that the case studies presented in this review will increase the visibility of lean stability, facilitate overcoming of the existing challenges, and accelerate the global regulatory acceptance of lean stability practices in the industry.

Ecological carrying capacity of alpine grassland in the Qinghai–Tibet Plateau based on the structural dynamics method - Yi-ping Fang; Fu-biao Zhu; Shu-hua Yi; Xiao-ping Qiu; Yong-jiang Ding (Environment, Development and Sustainability, 2021)

Unraveling the content of tail displays in an Asian agamid lizard - Xia Qiu; Qiaohan Hu; Richard Peters; Bisong Yue; Jinzhong Fu; Yin Qi (Behavioral Ecology and Sociobiology, 2021)

Garlic (Allium sativum) and Fu-ling (Poria cocos) mitigate lead toxicity by improving antioxidant defense mechanisms and chelating ability in the liver of grass carp (Ctenopharyngodon idella) - Haisu Liu; Sanshan Zhang; Ming Qiu; Anli Wang; Jianmin Ye; Shengli Fu (Ecotoxicology, 2021)

Systematic analysis of differentially expressed ZmMYB genes related to drought stress in maize - Peng-Yu Zhang; Xiao Qiu; Jia-Xu Fu; Guo-Rui Wang; Li Wei; Tong-Chao Wang (Physiology and Molecular Biology of Plants, 2021)

Correction to: Central Blockade of E-Prostanoid 3 Receptor Ameliorated Hypertension Partially by Attenuating Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus of Spontaneously Hypertensive Rats - Fang-Fang Wang; Juan Bai; Xiao-Jing Yu; Xiao-Lian Shi; Jin-Jun Liu; Kai-Li Liu; Li-Yan Fu; Qing Su; Hong-Bao Li; Kai B. Kang; Qiu-Yue Yi; Shu-Qiu Wang; et al. (Cardiovascular Toxicology, 2021)

Central Blockade of E-Prostanoid 3 Receptor Ameliorated Hypertension Partially by Attenuating Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus of Spontaneously Hypertensive Rats - Fang-Fang Wang; Juan Ba; Xiao-Jing Yu; Xiao-Lian Shi; Jin-Jun Liu; Kai-Li Liu; Li-Yan Fu; Qing Su; Hong-Bao Li; Kai B. Kang; Qiu-Yue Yi; Shu-Qiu Wang; et al. (Cardiovascular Toxicology, 2021)

TAPP1 Represses the Differentiation of Oligodendrocyte and its Deficiency Accelerates Myelin Regeneration after Demyelinating Injuries - Ruyi Mei; Jiaying Fu; Chunxia Jiang; Junlin Yang; Kang Zheng; Aifen Yang; Mengsheng Qiu; Xiaofeng Zhao (Neuroscience Bulletin, 2021)

In situ measurement of water accumulation in overlying goaf of coal mine-a transient electromagnetic-based study - Zhiyong Fu; Jian Kang; Dong-wei Qiu (Arabian Journal of Geosciences, 2021)

Modes of genetic adaptations underlying functional innovations in the rumen - Xiangyu Pan; Yudong Cai; Zongjun Li; Xianqing Chen; Rasmus Heller; Nini Wang; Yu Wang; Chen Zhao; Yong Wang; Han Xu; Songhai Li; Ming Li; et al. (Science China Life Sciences, 2021)

Sulfide ore prospecting in carbon-containing stratum using comprehensive time-domain induced polarization and controlled-source audio-frequency magnetotellurics - Ren-Bin Sun; Li-Xia Chu; Gui-Bin Zhang; Qiu-Ming Cheng; Yun-Chuan Xiang; Bin Hu; Chang-Rong Zhang; Jian-Fu Li; Yi-Jun Zhao (Applied Geophysics, 2020)

Improvements of the coupled WRF-Lake model over Lake Nam Co, Central Tibetan Plateau - Yang Wu; Anning Huang; Lazhu; Xianyu Yang; Bo Qiu; Lijuan Wen; Zhiqi Zhang; Zhipeng Fu; Xueyan Zhu; Xindan Zhang; Shuxin Cai; Yong Tang (Climate Dynamics, 2020)
A series of model sensitivity simulations are carried out to calibrate and improve the Weather Research and Forecasting Model coupled with a one-dimensional lake model (WRF-Lake) based on observations over Lake Nam Co. Using the default lake model parameters, the solution of WRF-Lake exhibits significant biases in both the lake thermodynamics and regional climatology, i.e., higher lake surface temperature (LST), earlier onset of summer thermal stratification, and overestimated near-surface air temperature and precipitation induced by the lake’s excessive warming and moistening impacts. The performance of WRF-Lake is improved through adjusting the initial lake temperature profile, the temperature of maximum water density (Tdmax), the surface roughness length, and the light extinction coefficient. Results show that initializing the water temperature with spring observation mitigates the LST overestimation and reduces the timing error of the onset of thermal stratification. By further adjusting Tdmax from 4 °C to the observed value of 3.5 °C, the LST increase from June to mid-July is enhanced and the buildup of thermal stratification is more accurately predicted. Through incorporating the parameterized surface roughness length and decreasing the light extinction coefficient, the model better reproduces the observed daily evolution of LST and vertical lake temperature profile. The calibrated WRF-Lake effectively mitigates the overestimation of over-lake air temperature at 2 m height and precipitation over regions downwind the lake. This suggests that an improved lake scheme within the coupled WRF-Lake is essential for realistically simulating the lake–air interactions and the regional climate over the lake-rich Tibetan Plateau.

The effect of baicalin on microRNA expression profiles in porcine aortic vascular endothelial cells infected by Haemophilus parasuis - Shulin Fu; Jun Liu; Jianfeng Xu; Sanling Zuo; Yunfei Zhang; Ling Guo; Yinsheng Qiu; Chun Ye; Yu Liu; Zhongyuan Wu; Yongqing Hou; Chien-An Andy Hu (Molecular and Cellular Biochemistry, 2020)

Reversal of Social Recognition Deficit in Adult Mice with MECP2 Duplication via Normalization of MeCP2 in the Medial Prefrontal Cortex - Bin Yu; Bo Yuan; Jian-Kun Dai; Tian-lin Cheng; Sheng-Nan Xia; Ling-Jie He; Yi-Ting Yuan; Yue-Fang Zhang; Hua-Tai Xu; Fu-Qiang Xu; Zhi-Feng Liang; Zi-Long Qiu (Neuroscience Bulletin, 2020)

SNX-2112, an Hsp90 inhibitor, suppresses cervical cancer cells proliferation, migration, and invasion by inhibiting the Akt/mTOR signaling pathway - Liang-Shun Fu; Hong-Hong Qiu; Min Liu; Liu-Bing Hu; Yan Wang; Peng-Chao Zhang; Man-Mei Li; Yi-Fei Wang; Zhong Liu (Medicinal Chemistry Research, 2020)

Flower injection of imidacloprid and spirotetramat: a novel tool for the management of banana thrips Thrips hawaiiensis - Buli Fu; Haiyan Qiu; Qiang Li; Liangde Tang; Dongqiang Zeng; Kui Liu; Yulin Gao (Journal of Pest Science, 2020)

Efficient photoreduction of Cr(VI) on TiO2/functionalized activated carbon (TiO2/AC-AEMP): improved adsorption of Cr(VI) and induced transfer of electrons - Zhao Gao; Hanpei Yang; Xiaofei Fu; Qiu Jin; Qiangshun Wu; Li Kang; Junming Wu (Environmental Science and Pollution Research, 2020)

The Potential Role of Marine Protein Hydrolyzates in Elevating Nutritive Values of Diets for Largemouth Bass, Micropterus salmoides - Min Dai; Songlin Li; Cefeng Fu; Hongjie Qiu; Naisong Chen (Frontiers in Marine Science, 2020)

Numerical simulation study of strip filling for water-preserved coal mining - Wei Bo Sun; Yan Wang; Hua Fu Qiu; Zi Wei Ding (Environmental Science and Pollution Research, 2020)

Bone marrow mesenchymal stem cell-secreted exosomes carrying microRNA-125b protect against myocardial ischemia reperfusion injury via targeting SIRT7 - Qi Chen; Yu Liu; Xueyan Ding; Qinfeng Li; Fuyu Qiu; Meihui Wang; Zhida Shen; Hao Zheng; Guosheng Fu (Molecular and Cellular Biochemistry, 2020)
MicroRNA-125b (miR-125b) reduces myocardial infarct area and restrains myocardial ischemia reperfusion injury (I/R). In this study, we aimed to investigate the effect of bone marrow mesenchymal stem cell (BMSC)-derived exosomes carrying miR-125b on I/R rats. The myocardial I/R model in rats was constructed by ligation of the left anterior descending coronary artery (LAD). Rats were randomly divided into I/R and Sham group. Lv-cel-miR-67 (control) or Lv-miR-125b was transfected into BMSCs. Exosomes were extracted from transfected BMSCs, and separately named BMSC-Exo-67, BMSC-Exo-125b, and BMSC-Exo. MTT assay and flow cytometry were used to detect the viability and apoptosis of I/R myocardium cells, respectively. The expression of cell apoptosis proteins and the levels of inflammatory factors were examined by Western blot and ELISA assay, respectively. The target relationship between miR-125b and SIRT7 was predicted by using StarBase3.0, and was confirmed by using dual-luciferase reporter gene assay. qRT-PCR, immunohistochemistry staining, and Western blot were used to evaluate the expression of SIRT7 in myocardium tissues in I/R rats. BMSC-derived exosomes were successfully isolated and identified by TEM and positive expression of CD9 and CD63. The expression of miR-125b was down-regulated in I/R myocardium tissues and cells. BMSC-Exo-125b significantly up-regulated miR-125b in I/R myocardium cells. The intervention of BMSC-Exo-125b significantly increased the cell viability, decreased the apoptotic ratio, down-regulated Bax and caspase-3, up-regulated Bcl-2, and decreased the levels of IL-1β, IL-6, and TNF-α in I/R myocardium cells. SIRT7 was a target of miR-125b, and BMSC-Exo-125b significantly down-regulated SIRT7 in myocardium cells. In addition, the injection of BMSC-Exo-125b alleviated the pathological damages and down-regulated SIRT7 in myocardium tissues of I/R rats. BMSC-derived exosomes carrying miR-125b protected against myocardial I/R by targeting SIRT7.

The protective function of non-coding DNA in DNA damage accumulation with age and its roles in age-related diseases - Guo-Hua Qiu; Xintian Zheng; Mingjun Fu; Cuiqin Huang; Xiaoyan Yang (Biogerontology, 2019)

Furanocoumarins with potential antiproliferative activities from Clausena lenis - Yan-Ping Liu; Qing Wen; Shi Hu; Yan-Lei Ma; Zhi-Hua Jiang; Jin-Ying Tang; Yan-Hui Fu; Shen-Xiang Qiu (Natural Product Research, 2019)

Influence of low molecular weight anionic ligands on the sorption of heavy metals by soil constituents: a review - Jun Zhu; Qingling Fu; Guohong Qiu; Yurong Liu; Hongqing Hu; Qiaoyun Huang; Antonio Violante (Environmental Chemistry Letters, 2019)

Spatial variation of the relationship between transport accessibility and the level of economic development in Qinghai-Tibet Plateau, China - Xue-ting Yang; Xiao-ping Qiu; Yi-ping Fang; Yun Xu; Fu-biao Zhu (Journal of Mountain Science, 2019)

Analysis of seasonal and annual field-evolved insecticide resistance in populations of Thrips hawaiiensis in banana orchards - Buli Fu; Haiyan Qiu; Qiang Li; Liangde Tang; Dongqiang Zeng; Kui Liu; Yulin Gao (Journal of Pest Science, 2019)

Oviposition, feeding preference, and biological performance of Thrips hawaiiensis on four host plants with and without supplemental foods - Buli Fu; Qiang Li; Haiyan Qiu; Liangde Tang; Dongqiang Zeng; Kui Liu; Yulin Gao (Arthropod-Plant Interactions, 2019)

Global Observations of Fine-Scale Ocean Surface Topography With the Surface Water and Ocean Topography (SWOT) Mission - Rosemary Morrow; Lee-Lueng Fu; Fabrice Ardhuin; Mounir Benkiran; Bertrand Chapron; Emmanuel Cosme; Francesco d’Ovidio; J. Thomas Farrar; Sarah T. Gille; Guillaume Lapeyre; Pierre-Yves Le Traon; Ananda Pascual; et al. (Frontiers in Marine Science, 2019)

Nutrition and water temperature regulate the expression of heat-shock proteins in golden pompano larvae (Trachinotus ovata, Limmaeus 1758) - Laetitia Allais; Chao Zhao; Mingjun Fu; Jing Hu; Jian G. Qin; Lihua Qiu; Zhenhua Ma (Fish Physiology and Biochemistry, 2019)

Evaluation of different trapping systems for the banana weevils Cosmopolites sordidus and Odoiporus longicollis - Buli Fu; Qiang Li; Haiyan Qiu; Liangde Tang; Xin Zhang; Kui Liu (International Journal of Tropical Insect Science, 2019)

Integrative genomic analysis predicts novel functional enhancer-SNPs for bone mineral density - Chuan Qiu; Hui Shen; Xiaoying Fu; Chao Xu; Qing Tian; Hongwen Deng (Human Genetics, 2019)

An analytical method for estimating leakage from a hydraulic pressure tunnel - Yong Huang; Huiyang Qiu; Zhi Dou; Zhimin Fu; Zhifang Zhou (Hydrogeology Journal, 2019)

Role of permafrost in resilience of social-ecological system and its spatio-temporal dynamics in the source regions of Yangtze and Yellow Rivers - Yi-ping Fang; Fu-biao Zhu; Shu-hua Yi; Xiao-ping Qiu; Yong-jian Ding (Journal of Mountain Science, 2019)

The IMPDH inhibitors, ribavirin and mycophenolic acid, inhibit peste des petits ruminants virus infection - Qiu-yan Chang; Fu-cheng Guo; Xue-rui Li; Jian-hua Zhou; Xuepeng Cai; Qiuwei Pan; Xiao-xia Ma (Veterinary Research Communications, 2018)

Down-regulation of microRNA-216a confers protection against yttrium aluminium garnet laser-induced retinal injury via the GDNF-mediated GDNF/GFRα1/RET signalling pathway - Xi-Bin Hu; Shu-Hua Fu; Qi Luo; Jian-Zhong He; Yan-Fei Qiu; Wei Lai; Min Zhong (Journal of Biosciences, 2018)

Adsorption of myo-inositol hexakisphosphate in water using recycled water treatment residual - Fuguo Qiu; Juanli Wang; Dongye Zhao; Kunming Fu (Environmental Science and Pollution Research, 2018)

Agromyces mangrovi sp. nov., a Novel Actinobacterium Isolated from Mangrove Soil - Ruijun Wang; Can Chen; Yue Su; Xiaoyun Yu; Chongya Zhang; Geyi Fu; Shuaibo Han; Xianmao Pan; Junming Qiu; Xiaopin Li; Min Wu (Current Microbiology, 2018)

Assessing spatial and temporal variations in regional sustainability in mainland China from 2004 to 2014 - Wei Qiu; Fanlin Meng; Yuntao Wang; Guangtao Fu; Junguo He; Dragan Savic; Hongyu Zhao (Clean Technologies and Environmental Policy, 2018)

Enhanced effect of EDDS and hydroxylamine on Fe(II)-catalyzed SPC system for trichloroethylene degradation - Xiaori Fu; Dionysios D. Dionysiou; Mark L. Brusseau; Waqas Qamar Zaman; Xueke Zang; Shuguang Lu; Zhaofu Qiu; Qian Sui (Environmental Science and Pollution Research, 2018)

Automatic 40Ar/39Ar Dating Techniques Using Multicollector ARGUS VI Noble Gas Mass Spectrometer with Self-Made Peripheral Apparatus - Xiu-Juan Bai; Hua-Ning Qiu; Wen-Gui Liu; Lian-Fu Mei (Journal of Earth Science, 2018)

Sp1 is an important transcriptional regulation factor for forkhead box N1 in pig - Dong Jie Zhang; Liang Wang; Zhong Qiu Li; Bo Fu; Guo Wei Yang; Di Liu (Journal of Genetics, 2018)

Effects of altitude on county economic development in China - Fu-biao Zhu; Yi-ping Fang; Xue-ting Yang; Xiao-ping Qiu; Hu Yu (Journal of Mountain Science, 2018)

Gradient effect of road transportation on economic development in different geomorphic regions - Xue-ting Yang; Yi-ping Fang; Xiao-ping Qiu; Fu-biao Zhu (Journal of Mountain Science, 2018)

UV‐B induced biosynthesis of a novel sunscreen compound in solar radiation and desiccation tolerant cyanobacteria - Jin‐Long Shang; Zhong‐Chun Zhang; Xiao‐Yue Yin; Min Chen; Fu‐Hua Hao; Kai Wang; Jun‐Li Feng; Hai‐Feng Xu; Yan‐Chao Yin; Hui‐Ru Tang; Bao‐Sheng Qiu (Environmental Microbiology, 2018)
Summary The small‐molecule sunscreen compounds, mycosporine‐like amino acids (MAAs), have strong ultraviolet (UV) absorption and can protect cyanobacteria against UV‐B damage. However, the molecular mechanism underlying UV‐B signaling and MAA chemical diversity remain largely unclear. Here, we identified a five‐gene cluster for MAA biosynthesis in the solar radiation and desiccation tolerant cyanobacterium Nostoc flagelliforme . A LuxR family protein OrrA was identified as a positive UV‐B responsive regulator binding to the promoter region of this gene cluster. OrrA functions as an activator mediating the UV‐B induced MAA biosynthesis. Overexpression of orrA strengthened its UV‐B tolerance during desiccation, and enhanced the photosynthetic recovery upon rehydration. Heterologous expression of this gene cluster in Anabaena PCC 7120 produces the same MAA as that in field samples of N . flagelliforme . The MAA structure is assigned as mycosporine‐2‐(4‐deoxygadusolyl‐ornithine) with a molecular weight of 756 Da, the structurally unique MAA compound reported to date. This MAA was catalyzed by mysD‐mysC2‐mysC1 encoding proteins from 4‐deoxygadusol, which was synthesized through the catalysis of mysA‐mysB products. Thus, we elucidated the transcriptional mechanism for a novel type MAA biosynthesis in solar radiation and desiccation tolerant cyanobacteria, which shed light on the identification of other components for UV‐B signaling in cyanobacteria.

Enhanced effect of HAH on citric acid-chelated Fe(II)-catalyzed percarbonate for trichloroethene degradation - Xiaori Fu; Mark L. Brusseau; Xueke Zang; Shuguang Lu; Xiang Zhang; Usman Farooq; Zhaofu Qiu; Qian Sui (Environmental Science and Pollution Research, 2017)

Potential gray matter unpruned in adolescents and young adults dependent on dextromethorphan-containing cough syrups: evidence from cortical and subcortical study - Ying-wei Qiu; Xiao-fei Lv; Gui-hua Jiang; Huan-Huan Su; Xiao-fen Ma; Jun-zhang Tian; Fu-zhen Zhuo (Brain Imaging and Behavior, 2017)

Aquatic animals promote antibiotic resistance gene dissemination in water via conjugation: Role of different regions within the zebra fish intestinal tract, and impact on fish intestinal microbiota - Jialun Fu; Dong Yang; Min Jin; Weili Liu; Xin Zhao; Chenyu Li; Tianyu Zhao; Jingfeng Wang; Zhixian Gao; Zhiqiang Shen; Zhigang Qiu; Jun‐Wen Li (Molecular Ecology, 2017)
The aqueous environment is one of many reservoirs of antibiotic resistance genes ( ARG s). Fish, as important aquatic animals which possess ideal intestinal niches for bacteria to grow and multiply, may ingest antibiotic resistance bacteria from aqueous environment. The fish gut would be a suitable environment for conjugal gene transfer including those encoding antibiotic resistance. However, little is known in relation to the impact of ingested ARG s or antibiotic resistance bacteria ( ARB ) on gut microbiota. Here, we applied the cultivation method, qPCR , nuclear molecular genetic marker and 16S rDNA amplicon sequencing technologies to develop a plasmid‐mediated ARG transfer model of zebrafish. Furthermore, we aimed to investigate the dissemination of ARG s in microbial communities of zebrafish guts after donors carrying self‐transferring plasmids that encode ARG s were introduced in aquaria. On average, 15% of faecal bacteria obtained ARG s through RP 4‐mediated conjugal transfer. The hindgut was the most important intestinal region supporting ARG dissemination, with concentrations of donor and transconjugant cells almost 25 times higher than those of other intestinal segments. Furthermore, in the hindgut where conjugal transfer occurred most actively, there was remarkable upregulation of the mRNA expression of the RP 4 plasmid regulatory genes, trbBp and trfAp . Exogenous bacteria seem to alter bacterial communities by increasing Escherichia and Bacteroides species, while decreasing Aeromonas compared with control groups. We identified the composition of transconjugants and abundance of both cultivable and uncultivable bacteria (the latter accounted for 90.4%–97.2% of total transconjugants). Our study suggests that aquatic animal guts contribute to the spread of ARG s in water environments.

Reservoir characteristics and methane adsorption capacity of the Upper Triassic continental shale in Western Sichuan Depression, China - Y. C. Liu; D. X. Chen; N. S. Qiu; Y. Wang; J. Fu; Y. Huyan; J. K. Jia; H. Wu (Australian Journal of Earth Sciences, 2017)

A novel non-ATP competitive FGFR1 inhibitor with therapeutic potential on gastric cancer through inhibition of cell proliferation, survival and migration - Jianzhang Wu; Xiaojing Du; Wulan Li; Yangyang Zhou; Encheng Bai; Yanting Kang; Qiuxiang Chen; Weitao Fu; Di Yun; Qing Xu; Peihong Qiu; Rong Jin; et al. (Apoptosis, 2017)

Molecular taxonomy and morphological characterization reveal new species and new host records of Torula species (Torulaceae, Pleosporales) - Jun-Fu Li; Rungtiwa Phookamsak; Rajesh Jeewon; Darbhe J. Bhat; Ausana Mapook; Erio Camporesi; Qiu-Ju Shang; Ekachai Chukeatirote; Ali H. Bahkali; Kevin D. Hyde (Mycological Progress, 2017)

GEM: a dynamic tracking model for mesoscale eddies in the ocean - Qiu-Yang Li; Liang Sun; Sheng-Fu Lin (Ocean Science, 2016)
The Genealogical Evolution Model (GEM) presented here is an efficient logical model used to track dynamic evolution of mesoscale eddies in the ocean. It can distinguish between different dynamic processes (e.g., merging and splitting) within a dynamic evolution pattern, which is difficult to accomplish using other tracking methods. To this end, the GEM first uses a two-dimensional (2-D) similarity vector (i.e., a pair of ratios of overlap area between two eddies to the area of each eddy) rather than a scalar to measure the similarity between eddies, which effectively solves the “missing eddy” problem (temporarily lost eddy in tracking). Second, for tracking when an eddy splits, the GEM uses both “parent” (the original eddy) and “child” (eddy split from parent) and the dynamic processes are described as the birth and death of different generations. Additionally, a new look-ahead approach with selection rules effectively simplifies computation and recording. All of the computational steps are linear and do not include iteration. Given the pixel number of the target region L, the maximum number of eddies M, the number N of look-ahead time steps, and the total number of time steps T, the total computer time is O(LM(N + 1)T). The tracking of each eddy is very smooth because we require that the snapshots of each eddy on adjacent days overlap one another. Although eddy splitting or merging is ubiquitous in the ocean, they have different geographic distributions in the North Pacific Ocean. Both the merging and splitting rates of the eddies are high, especially at the western boundary, in currents and in “eddy deserts”. The GEM is useful not only for satellite-based observational data, but also for numerical simulation outputs. It is potentially useful for studying dynamic processes in other related fields, e.g., the dynamics of cyclones in meteorology.

Application of high resolution SNP arrays in patients with congenital oral clefts in south China - TING-YING LEI; HONG-TAO WANG; FAN LI; YING-QIU CUI; FANG FU; RU LI; CAN LIAO (Journal of Genetics, 2016)

Using PG-Liposome-Based System to Enhance Puerarin Liver-Targeted Therapy for Alcohol-Induced Liver Disease - Ying-Zheng Zhao; Lu Zhang; Pardeep K. Gupta; Fu-Rong Tian; Kai-Li Mao; Kai-Yan Qiu; Wei Yang; Chuan-Zhu Lv; Cui-Tao Lu (AAPS PharmSciTech, 2016)

Wnt5a mediated canonical Wnt signaling pathway activation in orthodontic tooth movement: possible role in the tension force-induced bone formation - Hai-Di Fu; Bei-Ke Wang; Zi-Qiu Wan; Heng Lin; Mao-Lin Chang; Guang-Li Han (Journal of Molecular Histology, 2016)

Sensitivity of a regional climate model to land surface parameterization schemes for East Asian summer monsoon simulation - Wenkai Li; Weidong Guo; Yongkang Xue; Congbin Fu; Bo Qiu (Climate Dynamics, 2016)

Sleep and Cognitive Abnormalities in Acute Minor Thalamic Infarction - Wei Wu; Linyang Cui; Ying Fu; Qianqian Tian; Lei Liu; Xuan Zhang; Ning Du; Ying Chen; Zhijun Qiu; Yijun Song; Fu-Dong Shi; Rong Xue (Neuroscience Bulletin, 2016)

Event-related lateralized readiness potential correlates of the emotion-priming Simon effect - Qian Shang; Huijian Fu; Wenwei Qiu; Qingguo Ma (Experimental Brain Research, 2016)

A new plant assemblage from the Middle Triassic volcanic tuffs of Pingchuan, Gansu, northwestern China and its paleoenvironmental significance - Fu-Jun Ma; Qiu-Jun Wang; Jun-Ling Dong; Hao-Fei Wang; Zi-Xi Wang; Feng-Tai Zhang; Bai-Nian Sun (PalZ, 2016)

New material of Palaeocarya from the Oligocene of Ningming, Guangxi, South China - Jun-Ling Dong; Wen-Jia Wang; Peng Deng; Jin Wang; Fu-Jun Ma; Qiu-Jun Wang; Yi Yang; Bai-Nian Sun (PalZ, 2016)

Characterization, expression and silencing by RNAi of p53 from Penaeus monodon - Wenting Dai; Lihua Qiu; Chao Zhao; Mingjun Fu; Zhenhua Ma; Falin Zhou; Qibin Yang (Molecular Biology Reports, 2016)

Combinatorial enzymatic digestion with thermolysin and collagenase type I improved the isolation and culture effects of hair cell progenitors from rat cochleae - Yong-li Song; Ke-yong Tian; Wen-juan Mi; Peng Han; Zhong-jia Ding; Yang Qiu; Fu-quan Chen; Jian-jua Qiu (In Vitro Cellular & Developmental Biology - Animal, 2016)

Enhanced degradation of benzene by percarbonate activated with Fe(II)-glutamate complex - Xiaori Fu; Xiaogang Gu; Shuguang Lu; Zhouwei Miao; Minhui Xu; Xiang Zhang; Muhammad Danish; Hang Cui; Usman Farooq; Zhaofu Qiu; Qian Sui (Environmental Science and Pollution Research, 2016)

Anti-GAPDHS antibodies: a biomarker of immune infertility - Jun Fu; Rongyan Yao; Yanyun Luo; Dantong Yang; Yang Cao; Yi Qiu; Wei Song; Shiying Miao; Yiqun Gu; Linfang Wang (Cell and Tissue Research, 2016)

Measurement of aerosol effective density by single particle mass spectrometry - GuoHua Zhang; XinHui Bi; BingXue Han; Ning Qiu; ShouHui Dai; XinMing Wang; GuoYing Sheng; JiaMo Fu (Science China Earth Sciences, 2016)

Characterization and high expression of recombinant Ustilago maydis xylanase in Pichia pastoris - Hongjuan Han; Shuang You; Bo Zhu; Xiaoyan Fu; Baihui Sun; Jin Qiu; Chengye Yu; Lei Chen; Rihe Peng; Quanhong Yao (Biotechnology Letters, 2015)

Historical development and future perspectives of Environmental Specimen Bank in China: a mini review - Fang Qiu; Xiang-Zhou Meng; Yan-Ling Qiu; Qing-Hui Huang; Ying Liu; Ling-Ling Wu; Qian-Fen Xiao; Ya-Jie Sun; Rui Wang; Yi-Hui Zhou; Zhen-Yang Yu; Da-Qiang Yin; et al. (Environmental Science and Pollution Research, 2015)

The genetic basis of population fecundity prediction across multiple field populations of Nilaparvata lugens - Zhong Xiang Sun; Yi Fan Zhai; Jian Qing Zhang; Kui Kang; Jing Heng Cai; Yonggui Fu; Jie Qi Qiu; Jia Wei Shen; Wen Qing Zhang (Molecular Ecology, 2015)
Identifying the molecular markers for complex quantitative traits in natural populations promises to provide novel insight into genetic mechanisms of adaptation and to aid in forecasting population dynamics. In this study, we investigated single nucleotide polymorphisms ( SNP s) using candidate gene approach from high‐ and low‐fecundity populations of the brown planthopper ( BPH ) Nilaparvata lugens Stål (Hemiptera: Delphacidae) divergently selected for fecundity. We also tested whether the population fecundity can be predicted by a few SNP s. Seven genes ( ACE , fizzy, HMGCR , LpR, Sxl, Vg and VgR ) were inspected for SNP s in N. lugens , which is a serious insect pest of rice. By direct sequencing of the complementary DNA and promoter sequences of these candidate genes, 1033 SNP s were discovered within high‐ and low‐fecundity BPH populations. A panel of 121 candidate SNP s were selected and genotyped in 215 individuals from 2 laboratory populations ( HFP and LFP ) and 3 field populations ( GZP , SGP and ZSP ). Prior to association tests, population structure and linkage disequilibrium ( LD ) among the 3 field populations were analysed. The association results showed that 7 SNP s were significantly associated with population fecundity in BPH . These significant SNP s were used for constructing general liner models with stepwise regression. The best predictive model was composed of 2 SNP s ( ACE ‐862 and VgR ‐816 ) with very good fitting degree. We found that 29% of the phenotypic variation in fecundity could be accounted for by only two markers. Using two laboratory populations and a complete independent field population, the predictive accuracy was 84.35–92.39%. The predictive model provides an efficient molecular method to predict BPH fecundity of field populations and provides novel insights for insect population management.

Genome re-sequencing suggested a weedy rice origin from domesticated indica-japonica hybridization: a case study from southern China - Jie Qiu; Jinwen Zhu; Fei Fu; Chu-Yu Ye; Weidi Wang; Linfeng Mao; Zhangxiang Lin; Li Chen; Haiqiang Zhang; Longbiao Guo; Shen Qiang; Yongliang Lu; et al. (Planta, 2014)

Jurassic lacustrine source rock characteristics and its petroleum geological significance in the Southeast Depression of Tarim Basin, China - Zhenglong Jiang; Haijun Qiu; Yuping Huang; Wenkang Fu; Kunpeng Jiang; Ji Chen (Arabian Journal of Geosciences, 2014)

Shift in abundance and structure of soil ammonia-oxidizing bacteria and archaea communities associated with four typical forest vegetations in subtropical region - Yong-Chun Li; Bu-Rong Liu; Song-Hao Li; Hua Qin; Wei-Jun Fu; Qiu-Fang Xu (Journal of Soils and Sediments, 2014)

The toxicity of cerium nitrate to Elodea canadensis: subcellular distribution, chemical forms and physiological effects - Wei Yue Chu; San Juan Cai; Yong Yang Fu; Fei Fei Li; Ting Xu; Han Qiu; Qin Song Xu (Acta Physiologiae Plantarum, 2014)

Effect of dietary lysine on growth, intestinal enzymes activities and antioxidant status of sub-adult grass carp (Ctenopharyngodon idella) - Xue-Yin Li; Ling Tang; Kai Hu; Yang Liu; Wei-Dan Jiang; Jun Jiang; Pei Wu; Gang-Fu Chen; Shu-Hong Li; Sheng-Yao Kuang; Lin Feng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2014)

Geochronology and geochemistry of the Late Triassic Longtan pluton in South China: termination of the crustal melting and Indosinian orogenesis - Liang Qiu; Dan-Ping Yan; Mei-Fu Zhou; Nicholas T. Arndt; Shuang-Li Tang; Liang Qi (International Journal of Earth Sciences, 2014)

Occurrence and removal of six pharmaceuticals and personal care products in a wastewater treatment plant employing anaerobic/anoxic/aerobic and UV processes in Shanghai, China - Dan Wang; Qian Sui; Shu-Guang Lu; Wen-Tao Zhao; Zhao-Fu Qiu; Zhou-Wei Miao; Gang Yu (Environmental Science and Pollution Research, 2014)

Molecular Cloning and Characterization of a Trichome-Specific Promoter of Artemisinic Aldehyde Δ11(13) Reductase (DBR2) in Artemisia annua - Weimin Jiang; Xu Lu; Bo Qiu; Fangyuan Zhang; Qian Shen; Zongyou Lv; Xueqing Fu; Tingxiang Yan; Erdi Gao; Mengmeng Zhu; Lingxian Chen; Ling Zhang; et al. (Plant Molecular Biology Reporter, 2014)

Bioaccumulation, subcellular, and molecular localization and damage to physiology and ultrastructure in Nymphoides peltata (Gmel.) O. Kuntze exposed to yttrium - Yongyang Fu; Feifei Li; Ting Xu; Sanjuan Cai; Weiyue Chu; Han Qiu; Sha Sha; Guangyu Cheng; Qinsong Xu (Environmental Science and Pollution Research, 2014)

Study on the Effect of Kidney Transplantation on the Health of the Patients’ Offspring: A Report on 252 Chinese Children - Longgen Xu; Peng Han; Yong Liu; Hongwei Wang; Yirong Yang; Feng Qiu; Wanling Peng; Ligong Tang; Jing Fu; Xiaofeng Zhu; Youhua Zhu (Cell Biochemistry and Biophysics, 2014)

Age-dependent association of KIBRA gene polymorphism with Alzheimer’s disease in Han Chinese - Hui-Fu Wang; Lan Tan; Jin-Tai Yu; Xiao-Ying Ma; Qiu-Yan Liu; Wei Wang (Molecular Biology Reports, 2013)

Copper ultrastructural localization, subcellular distribution, and phytotoxicity in Hydrilla verticillata (L.f.) Royle - Qinsong Xu; Han Qiu; Weiyue Chu; Yongyang Fu; Sanjuan Cai; Haili Min; Sha Sha (Environmental Science and Pollution Research, 2013)

Influence of HbA1c on short-term blood pressure variability in type 2 diabetic patients with diabetic nephropathy - Fang Liu; Min Wu; Yan-huan Feng; Hui Zhong; Tian-lei Cui; You-qun Huang; Ya-ping Liang; Yong-shu Diao; Li Zang; Ling Li; Jing Zang; Hong-yu Qiu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

A new flavanocoumarin from the root of Flemingia philippinensis - Manqin Fu; Dun Deng; Riming Huang; Nenling Zhang; Zhiwei Su; Samuel X. Qiu (Natural Product Research, 2013)

Association of TOMM40 Polymorphisms with Late-Onset Alzheimer’s Disease in a Northern Han Chinese Population - Xiao-Ying Ma; Jin-Tai Yu; Wei Wang; Hui-Fu Wang; Qiu-Yan Liu; Wei Zhang; Lan Tan (NeuroMolecular Medicine, 2013)

The Influence of Cu(II) on the Formation and Distribution of Disinfection By-Products during the Chlorination of Drinking Water - Shao-gang Liu; Zhi-liang Zhu; Xue-cai Tan; Xin-hui Feng; Zai-yin Huang; Yan-ling Qiu; Jian-fu Zhao (Water, Air, & Soil Pollution, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Candida sanyaensis sp. nov., an ascomycetous yeast species isolated from soil - Feng-Li Hui; Qiu-Hong Niu; Tao Ke; Ying-Xia Li; Ching-Fu Lee (Antonie van Leeuwenhoek, 2013)

Protective effect of low-molecular-weight heparin on pancreatic encephalopathy in severe acute pancreatic rats - Fu Qiu; Xin-sheng Lu; Yu-kun Huang (Inflammation Research, 2012)

Analysis of 2,297 expressed sequence tags (ESTs) from a cDNA library of flax (Linum ustitatissimum L.) bark tissue - Song-Hua Long; Xin Deng; Yu-Fu Wang; Xiang Li; Rui-Qing Qiao; Cai-Sheng Qiu; Yuan Guo; Dong-Mei Hao; Wan-Qi Jia; Xin-Bo Chen (Molecular Biology Reports, 2012)

Molecular characterization and expression analysis of dihydroflavonol 4-reductase (DFR) gene in Saussurea medusa - Houhua Li; Jian Qiu; Fudong Chen; Xiaofen Lv; Chunxiang Fu; Dexiu Zhao; Xuejun Hua; Qiao Zhao (Molecular Biology Reports, 2012)

An efficient regeneration system via direct and indirect organogenesis for the medicinal plant Dysosma versipellis (Hance) M. Cheng and its potential as a podophyllotoxin source - Weimei Jiang; Luxi Chen; Qi Pan; Yingxiong Qiu; Yingying Shen; Chengxin Fu (Acta Physiologiae Plantarum, 2012)

Induced bone marrow mesenchymal stem cells improve cardiac performance of infarcted rat hearts - Xiao-Hong Li; Yong-Heng Fu; Qiu-Xiong Lin; Zai-Yi Liu; Zhi-Xin Shan; Chun-Yu Deng; Jie-Ning Zhu; Min Yang; Shu-Guang Lin; Yangxin Li; Xi-Yong Yu (Molecular Biology Reports, 2012)

17beta-estradiol attenuates pressure overload-induced myocardial hypertrophy through regulating caveolin-3 protein in ovariectomized female rats - Yu-Hong Cui; Zhi Tan; Xiao-Dong Fu; Qiu-Ling Xiang; Jin-Wen Xu; Ting-Huai Wang (Molecular Biology Reports, 2011)

Chemical composition and antioxidant activity of the essential oil of endemic Viola tianshanica - Jin Yang; Zhen Qu; Yu-Ling Xiao; Guo-Fu Qiu; Tao Zhang; Zhong-Yuan Wu; Xian-Ran He; Xian-Ming Hu (Natural Product Research, 2011)

Insights into the pH up-shift responsive mechanism of Acidithiobacillus ferrooxidans by microarray transcriptome profiling - Qian Li; Youhua Ren; Guanzhou Qiu; Nuo Li; Hongwei Liu; Zhimin Dai; Xian Fu; Li Shen; Yili Liang; Huaqun Yin; Xueduan Liu (Folia Microbiologica, 2011)

The Community Dynamics of Major Bioleaching Microorganisms During Chalcopyrite Leaching Under the Effect of Organics - Qihou Li; Ye Tian; Xian Fu; Huaqun Yin; Zhijun Zhou; Yiting Liang; Guanzhou Qiu; Jie Liu; Hongwei Liu; Yili Liang; Li Shen; Jing Cong; et al. (Current Microbiology, 2011)

Polycyclic aromatic hydrocarbons in surface sediments of the Jialu River - Jie Fu; Sheng Sheng; Teng Wen; Zhi-Ming Zhang; Qing Wang; Qiu-Xiang Hu; Qing-Shan Li; Shu-Qing An; Hai-Liang Zhu (Ecotoxicology, 2011)

Geochemical changes of the terrigenous sediments in the southern South China Sea and their paleoenvironmental implications during the last 31 ky - Shuqing Fu; Zhaoyu Zhu; Tingping Ouyang; Yan Qiu; Zhenquan Wei (Journal of Oceanography, 2011)

Overyielding and interspecific interactions mediated by nitrogen fertilization in strip intercropping of maize with faba bean, wheat and barley - Qiu-Zhu Li; Jian-Hao Sun; Xiao-Jing Wei; Peter Christie; Fu-Suo Zhang; Long Li (Plant and Soil, 2011)

Involvement of recF in 254 nm Ultraviolet Radiation Resistance in Deinococcus radiodurans and Escherichia coli - Xiaosong Chang; Lan Yang; Qing Zhao; Wenjuan Fu; Hao Chen; Zhiqun Qiu; Ji-an Chen; Ran Hu; Weiqun Shu (Current Microbiology, 2010)

Spatio-Temporal Variability of Soil Respiration of Forest Ecosystems in China: Influencing Factors and Evaluation Model - Ze-Mei Zheng; Gui-Rui Yu; Xiao-Min Sun; Sheng-Gong Li; Yue-Si Wang; Ying-Hong Wang; Yu-Ling Fu; Qiu-Feng Wang (Environmental Management, 2010)

Effects of Artemisinin Derivative on the Growth Metabolism of Tetrahymena thermophila BF5 Based on Expression of Thermokinetics - Xue-Song Shen; Qi Su; Zhuang-ping Qiu; Jing-yi Xu; Yan-xia Xie; Han-fu Liu; Yi Liu (Biological Trace Element Research, 2010)

Pancreatic somatostatinoma with obscure inhibitory syndrome and mixed pathological pattern - Bo Zhang; Qiu-ping Xie; Shun-liang Gao; Yan-biao Fu; Yu-lian Wu (Journal of Zhejiang University-SCIENCE B, 2010)

Stabilization of hepatocyte growth factor mRNA by hypoxia-inducible factor 1 - Sheng-Hua Chu; Dong-Fu Feng; Yan-Bin Ma; Zhi-An Zhu; Hong Zhang; Jian-Hua Qiu (Molecular Biology Reports, 2009)

Previous pulmonary disease and family cancer history increase the risk of lung cancer among Hong Kong women - Xiao-Rong Wang; Ignatius T. S. Yu; Yuk Lan Chiu; Hong Qiu; Zhenming Fu; William Goggins; Joseph S. K. Au; Lap-Ah Tse; Tze-Wai Wong (Cancer Causes & Control, 2009)

Estrogen receptor expression in adrenocortical carcinoma - Xiao-cao Shen; Cai-xiao Gu; Yi-qing Qiu; Chuan-jun Du; Yan-biao Fu; Jian-jun Wu (Journal of Zhejiang University-SCIENCE B, 2009)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Isolation and characterization of microsatellite markers in Dysosma versipellis (Berberidaceae), a rare endemic from China - Bi-Cai Guan; Ying-Xiong Qiu; Cheng-Xin Fu (Conservation Genetics, 2008)

Quantifying biochemical variables of corn by hyperspectral reflectance at leaf scale - Qiu-xiang Yi; Jing-feng Huang; Fu-min Wang; Xiu-zhen Wang (Journal of Zhejiang University-SCIENCE B, 2008)

Genetic Diversity and Geographic Differentiation in the Threatened Species Dysosma pleiantha in China as Revealed by ISSR Analysis - Min Zong; Hai-Long Liu; Ying-Xiong Qiu; Shu-Zhen Yang; Ming-Shui Zhao; Cheng-Xin Fu (Biochemical Genetics, 2008)

Protective effects of ginsenoside Rg3 against cyclophosphamide-induced DNA damage and cell apoptosis in mice - Qiu Hua Zhang; Chun Fu Wu; Lian Duan; Jing Yu Yang (Archives of Toxicology, 2008)

Cloning, expression, and pharmacological activity of BmK AS, an active peptide from scorpion Buthus martensii Karsch - Jian-Hua Shao; Yue-Qiu Wang; Xiao-Yan Wu; Rui Jiang; Rong Zhang; Chun-Fu Wu; Jing-Hai Zhang (Biotechnology Letters, 2007)

Isolation of a strain of Acidithiobacillus caldus and its role in bioleaching of chalcopyrite - Qiu Guan Zhou; Fu Bo; Zhou Hong Bo; Liu Xi; Gao Jian; Liu Fei Fei; Chen Xin Hua (World Journal of Microbiology and Biotechnology, 2007)

Learning from Viruses: The Necrotic Bodies of Tumor Cells with Intracellular Synthetic dsRNA Induced Strong Anti-tumor Immune Responses - Zhengrong Cui; Uyen M. Le; Fu Qiu; Dalia S. Shaker (Pharmaceutical Research, 2007)

Genes expression analyses of sea-island cotton (Gossypium barbadense L.) during fiber development - Li-Li Tu; Xian-Long Zhang; Shao-Guang Liang; Di-Qiu Liu; Long-Fu Zhu; Fan-Chang Zeng; Yi-Chun Nie; Xiao-Ping Guo; Feng-Lin Deng; Jia-Fu Tan; Li Xu (Plant Cell Reports, 2007)

Species-specific SCAR markers for authentication of Sinocalycanthus chinensis - Qian Ye; Ying-xiong Qiu; Yan-qi Quo; Jian-xin Chen; Shu-zhen Yang; Ming-shui Zhao; Cheng-xin Fu (Journal of Zhejiang University-SCIENCE B, 2006)

Phylogenetic Relationships and Possible Hybrid Origin of Lycoris Species (Amaryllidaceae) Revealed by ITS Sequences - Shude Shi; Yingxiong Qiu; Enxiang Li; Ling Wu; Chengxin Fu (Biochemical Genetics, 2006)

The Mechanism of Involuntary Visual Spatial Attention Revealed by a New Linear Computation Model - Lijun Qiu; Dezhong Yao; Shimin Fu; Lin Chen (Brain Topography, 2006)

The seasonal variabilities in the concentration of atmospheric aerosols over Qingdao, China - Lifang Sheng; Ying Fu; Mingyan Qiu; Huiwang Gao (Journal of Ocean University of China, 2005)

The effects of land use on runoff and soil nutrient losses in a gully catchment of the hilly areas: implications for erosion control - Wang Jun; Fu Bojie; Qiu Yang; Chen Liding; Chen Chen; Hu Baodong (Journal of Geographical Sciences, 2005)

Use of oligonucleotide fingerprinting and faecal DNA in identifying the distribution of the Chinese tiger (Panthera tigris amoyensis Hilzheimer) - Qiu-Hong Wan; Sheng-Guo Fang; Guo-Fu Chen; Zhang-Ming Wang; Ping Ding; Mu-Yuan Zhu; Kong-Shou Chen; Jiu-Hua Yu; Yue-Ping Zhao (Biodiversity and Conservation, 2003)

Genetic susceptibility to pre-eclampsia and chromosome 7q36 - G. Guo; J.A. Lade; A.N. Wilton; E.K. Moses; M. Grehan; Y. Fu; H. Qiu; D.W. Cooper; S.P. Brennecke (Human Genetics, 1999)

Genetic susceptibility to pre-eclampsia and chromosome 7q36 - G. Guo; J.A. Lade; A.N. Wilton; E.K. Moses; M. Grehan; Y. Fu; H. Qiu; D.W. Cooper; S.P. Brennecke (Human Genetics, 1999)